GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 577245562 species occurrences available in GBIF matching the query: All data. The dataset includes 577245562 records from 13187 constituent datasets: 1 records from Oribates picipes. 1428 records from Shellfish (GNHM-MS). 76 records from Birdrace-Birding_for_Nature-Bonn. 2 records from Haselbachtal. 2 records from Hildener Heide - Spörkelnbruch (Haan). 133 records from Wulfsmuehle/Pinnau. 13 records from Collection Reptilia fossil SMF. 101 records from Steinbruch Kronungen. 2546 records from The atlas of butterflies in Kraków. 1 records from Zetes dorsalis. 1 records from Zetes morticinus. 68 records from Sandhofen. 13403 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 1 records from Hypochthonius rufulus. 25371 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 96 records from Birdrace-Berlin_Sparrows-Uckermark. 126 records from Total foraminifera counts of multinet M11/1_MSN517. 398 records from Tsetse flies of East Africa update. 1252 records from Aquatic Coleoptera Conservation Trust - SNH site condition monitoring of SSSIs for water beetles 2010. 15 records from Taxonomy of European Damaeidae (Acari: Oribatida) I. Kunstidamaeus Miko, 2006, with comments on Damaeus sensu lato. 511 records from Coleoptera of Swierklaniec Forest. 1722 records from Cambridgeshire & Peterborough Biological Records Centre - Orthoptera dataset held by CPERC. 45 records from Scottish Natural Heritage - Surveys of Najas flexilis (Slender naiad) in Scotland 2004 â 2011. 583 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-847B. 7410 records from Helgeland Museum, Lepidoptera. 418 records from Type Collection of the Seto Marine Biological Laboratory, Kyoto University. 91 records from Birdrace-Enger_am_Spektiv-Herford. 86 records from Besonderer Ort - besondere Natur: Die Mainzer Zitadelle. 49 records from Schulgartengelände des Hans-Carossa-Gymnasiums (Berlin). 98 records from Rund ums Cani. 78 records from Birdrace-Die_Laufenten-Braunschweig. 13 records from FND "Weißer Berg" Leißling. 15 records from Kirchheller Heide ( Bottrop). 1023 records from (Appendix Table 1) Number of planktonic foraminiferal genera and species in Late Creatceous sediments of ODP Hole 122-762C from the Exmouth Plateau, eastern Indian Ocean. 169 records from Plasm bearing foraminifera counts from M35/1_MSN1048. 299 records from Total foraminifera counts of multinet M21/3_MSN662. 116 records from Phytoplankton abundance and species composition in the Sicily Channel in October 1991. 6 records from Nannofossil abundance of Hole 67-494A. 15 records from Diatom abundance measured on water bottle samples at station PS58/090-4. 255 records from Planktic foraminifera counts of sediment core RC09-150. 31 records from Aktionstag Wiese am Vogelhammerkopf. 6 records from Rango, comportamiento, tamaño de población y conservación de felinos en el Volcán de Colima. 2427 records from Ibaraki Nature Museum, Mollusk collection. 811 records from U. S. National Parasite Collection's holdings from Robert L. Rausch. 41548 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1985) (AfrOBIS). 19164 records from The Gordon Alexander Orthoptera Collection. 1684 records from MfN Fish Collection, Zoology. 3 records from Analyses of the recent components of sediment core PS1215-2. 196 records from Unser kleines Rasenstück/ Dürer-Gymnasium Nürnberg. 4 records from Occurrence of mammalia relicts at site Ahlen. 45 records from Pseudecheneis maurus, a new species of glyptosternine catfish (Teleostei: Sisoridae) from Central Vietnam.. 2 records from Simpsonichthys suzarti sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual fish from the Rio Pardo floodplains, northeastern Brazil.. 3762 records from Inventaire National du Patrimoine Naturel : Flore protégée du Dauphiné. 24469 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Anfibios. 126 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, >125 µm fraction. 128 records from Total foraminifera counts of multinet M42/3_MSN1359. 136 records from Total foraminifera counts of multinet PO247/2_MSN1380. 35 records from Planktic foraminifera of sediment core GeoB1404-3. 215 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 2 records from (Fig. 5) Pollen analysis of the Furo do Chato core. 20 records from The interstitial subsoil fauna of the medium beach level at Sarso Beach, Red Sea (Table 3). 3709 records from Plant (MNHM-PL). 16604 records from Iberian Odonata distribution: data of the BOS Arthropod Collection (Univ. Oviedo, Spain). 871 records from (Appendix D) Analyses of the benthic foraminifer assemblage at ODP Hole 112-680B. 52181 records from ANTARCTIC PLANT DATABASE. 127133 records from Fish specimens. 1358 records from Electron Micrograph Database (Australian Antarctic Data Centre). 1353 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC12-294. 195 records from Altenburg bei Bamberg. 22 records from Occurrence of mammalia relicts at site Castlepook Cave. 808 records from Range table from planktonic foraminifers in ODP Hole 154-925B. 394 records from Range table from benthic foraminifers in ODP Hole 144-871C. 1460 records from Range table from benthic foraminifers in ODP Hole 151-909C. 631 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 149-898A. 122 records from Relative abundance of benthic foraminifera of sediment core GIK13292-3, East Atlantic off Senegal and Gambia (Table 3). 290333 records from AMNH Mammal Collections. 172 records from Redescription of Gymnotus coropinae (Gymnotiformes, Gymnotidae), an often misidentified species of Neotropical electric fish, with notes on natural history and electric signals.. 4390 records from Orthoptera collection (EO) of the Muséum national d'Histoire naturelle (MNHN - Paris). 74 records from Birdrace_Gätkes_Schergen-Helgoland. 45 records from Nannofossil abundance of Hole 64-481A. 16 records from Nannofossil abundance of Hole 11-106B. 221 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Turdidae. 11 records from Microzooplankton abundance and biomass at station TT043_17-1. 11 records from Microzooplankton abundance and biomass at station TT045_4-1. 6 records from Microzooplankton abundance and biomass at station NBP97-08-37-4. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-10-2. 26 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/357-1. 182 records from Biotope entdecken im Kockmecker Siepen (Sauerland). 62 records from Abundance of coccosphere-units of sediment core GIK23400-3. 13 records from Diatom abundance measured on water bottle samples at station PS58/042-2. 22 records from Geophagus abalios, G. dicrozoster and G. winemilleri (Perciformes: Cichlidae), three new species from Venezuela.. 565 records from Biodiversidad de productores primarios de lagunas costeras del norte de Yucatán, México_2. 578 records from (Table 3) Relative abundances of selected planktonic foraminifera of ODP Site 117-722. 321 records from Nova Scotia Department of Natural Resources, Subenacadie, NS, Canada. 43 records from Vogelstimmenführung durch den Tiergarten. 85 records from Unterbrucker Weiher. 181 records from Occurrence of mammalia relicts at site Kemathenhöhle. 123 records from Range table from planktonic foraminifers in ODP Hole 180-1111A. 27 records from Benthic foraminifera and algae abundance of Hole 81-553. 169 records from Whale log - observations from ANARE voyages. 156 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 317 records from Terrestrial Heteroptera Recording Scheme (Shieldbugs & allied species) - iSpot (2008-2010): Shieldbugs & allied species. 1180 records from Nottinghamshire Biological and Geological Records Centre - Nottinghamshire Water Vole Records. 6 records from Synodontis acanthoperca, a new species from the Ogooue River system, Gabon with comments on spiny ornamentation and sexual dimorphism in mochokid catfishes (Siluriformes: Mochokidae).. 1 records from Hoplophora decumana. 4 records from Microzooplankton abundance and biomass at station TT050_26-17. 6 records from Wiese. 702 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 1470 records from (Table 10) Distribution of planktonic foraminifers in ODP Hole 108-662A. 20 records from Distribution of planktonic foraminifera and other biogenic components in ODP Hole 113-693A (Figure 2). 3045 records from Obtención de la riqueza de aves y selección de especies susceptibles de monitoreo en la zona noroeste en el estado de Chiapas. 368 records from Great Lakes Forestry Centre Insect Collection. 109504 records from Plant Specimens of Kurashiki Museum of Natural History. 36254 records from Fish collection of National Museum of Nature and Science. 46156 records from Zooplankton in the bay of Biscay (1995-2004 Yearly spring DEPM surveys). 399 records from Colecciones Zoológicas de la Universidad de León, Colección de Poliquetos. 354 records from Foraminifera distribution of sediment core KS310. 160757 records from Slovenian Fungal Database - Boletus informaticus. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station AUGUST-1994-D4. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station MAY-1995-D4. 19 records from Occurrence of mammalia relicts at site Gröbern. 68 records from Occurrence of mammalia relicts at site l´Abri du Morin. 48 records from Range table from planktonic foraminifers in ODP Hole 180-1116A. 17 records from Benthic foraminifera abundance of Hole 11-108. 3324 records from Crustacea collection of the Finnish Museum of Natural History. 1740 records from Monitoring data from the federal state Berlin (Germany). 6943 records from DMNS Egg Collection (Arctos). 25793 records from NCOS1959_Crustacea (OBIS China). 61 records from A taxonomic revision of the catshark genus Holohalaelurus Fowler 1934 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae), with descriptions of two new species.. 218 records from (Table 6) Benthic foraminiferal genera in DSDP Core 95-612-5. 176 records from (Appendix E) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 161-976C. 1320 records from (Table 8D) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 15-4 through 19-3. 227 records from Colección de Salamandras Museo de La Salle Bogotá (MLS). 2391 records from Ohio State University Tetrapod Division - Reptile Collection (OSUM). 40 records from Coccolith counts of multinet M32/5_MSN979. 4702 records from Amphibian specimens. 12836 records from Planktic foraminifera assemblage in sediment core MD97-2142. 27 records from Herbarium Senckenbergianum (FR) - Protista. 85 records from Schulgelände IGS Kaufungen. 35 records from Occurrence of mammalia relicts at site Gura Cheii-Rasnov. 376 records from Planktic foraminifera abundance of Hole 22-216. 1790 records from Planktic foraminifera abundance of Hole 9-77B. 1845 records from (Table 8C) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 8-5 through 15-3. 132 records from Range table from benthic foraminifers in ODP Hole 144-876A. 1 records from A new species of Asphinctopone (Hymenoptera: Formicidae: Ponerinae) from Tanzania.. 320 records from Scottish Wildlife Trust - Ants: Formica Exsecta Records from Abernethy RSPB. 99 records from G.B. Pant Institute of Himalayan Environment & Development - Plants of West Himalaya, India. 781 records from RSPB - Bittern Annual Surveys in Britain 1990-2008 (SCARABBS). 99 records from Streuobstwiese Stedar. 248 records from Schulgarten der Volksschule. 77152 records from Conchological Society of Great Britain & Ireland - Mollusc (marine) data for Great Britain and Ireland. 22978 records from Humber Environmental Data Centre - Humber Environmental Data Centre - Non Sensitive Records from all taxonomic groups. 3065 records from Colección de Ofidios Museo de La Salle Bogotá (MLS). 79 records from Plasm bearing foraminifera counts of multinet M21/2_MSN628. 5 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_818-16. 45 records from (Table A.09) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (125-250 µm). 2 records from Range table from nannofossils in ODP Hole 198-1207A. 3524 records from Escarabajos y moscas de los bosques de niebla del sureste mexicano (Coleoptera: Scarabaeoidea; Diptera: Syrphidae y Calliphoridae). 7208 records from Catálogo y base de datos preliminar de la flora de Sinaloa. 2 records from Akita Prefectural Museum＋Hagfishes Specimens of Akita Prefectural Museum. 66 records from (Appendix A5) Relative abundances of planktonic foraminifera of sediment core GeoB1711-5. 16 records from Occurrence of mammalia relicts at site Dorog. 69 records from Planktic foraminifera abundance of Hole 52-418. 534 records from Leopard Seal census, Heard Island 1987/88. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 22224 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 166 records from BIRDRACE Die Düsselmöwen. 106 records from BIRDRACE EFTAS-NLU Birdrace Team 2008. 28934 records from Coleção de Abelhas do Museu de Ciências e Tecnologia da PUCRS. 305 records from Flux data of NU2_trap (Table A1). 109 records from Dreilinden Gymnasium-Schulgelände. 5570 records from HBRA - Herbário do Instituto de Estudos Costeiros da Universidade Federal do Pará. 1 records from Tunicata ZMK. 36 records from Salzwiese Diekskiel. 41 records from Abundance of living benthic foraminifera in sediment core CD86_07_BC4. 1 records from Microplankton counts and carbon biomass at station TT011_8-CTD96. 50 records from Leben in den Elbwiesen. 19386 records from Base de datos de aves mexicanas del Natural History Museum, Tring, Inglaterra. 4540 records from Inventario de la mastofauna en las reservas de la biosfera Desierto del Vizcaíno y Valle de los Cirios. 62 records from Phytoplankton abundance during Akademik Vernadsky cruise AV22. 3538 records from (Table 4) Paleocene to Eocene planktonic foraminifera of DSDP Hole 29-277. 13960 records from Collection Trichoptera - SMF. 7 records from Collection Malakologie - SMNG. 21172 records from Weddell Seal Sightings, Vestfold Hills, Antarctica. 18473 records from Australian Antarctic Division Herbarium. 1289 records from Percentages of planktonic foraminifera species in sediment core V22-222. 1304 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-127. 495 records from (Table A.08) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (80-150 µm). 691 records from Foraminifera abundance of Hole 24-236. 1035 records from Foraminifera abundance of Hole 24-237. 130 records from Range table from planktonic foraminifers in ODP Hole 139-855C. 62371 records from MLZ Bird Collection (Arctos). 3201 records from Weevils of the Carpathians. 10271 records from Carabidae of Poland. 2421 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 13 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/061-3. 3 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_832-7. 15 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_10-CTD124. 16 records from Phytoplankton abundance at station Sechin_2003-12-03_1, Casma, Peru. 12 records from Distribution of meiobenthos in sediment core M19_239-2 of the northeastern Atlantic (Table 1). 81 records from (Table 2) Absolute abundance of Contusotruncana contusa in DSDP Hole 74-527. 240 records from Coleoptera identified from the Woolwich Manor Way site, Becton, London. 18 records from Nannofossil abundance of Hole 8-73. 394 records from (App 7) Relative contents of benthic foraminifera species in sediments accumulated during last 1000 years, Core ASV11-987. 7 records from Appendicularia abundance of station M9_C near the Great Meteor Bank, Northeast Atlantic (Table 2). 83 records from Occurrence of mammalia relicts at site Spitzbubenhöhle. 98 records from Planktic foraminifera abundance of Hole 74-528. 427 records from Planktic foraminifera abundance of Hole 76-533A. 38 records from Dinoflagellate abundance of Hole 71-512. 3536 records from Live (Rose Bengal stained) benthic foraminifera of surface sediments of the Persian Gulf (Table 1). 10792 records from Fungi specimen detabase of Kanagawa Prefectural Museum of Natural History. 141 records from VFD-BW, Schönbuch: Pferdeweiden Breitenstein. 1 records from Orthoptera - SMF. 811 records from Amphibians and reptiles of Ireland. 621 records from Biological Records Centre - UK Ladybird Survey data from iRecord. 14 records from Radiolaria assemblage in sediment core GIK23259-2. 66 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 113-689. 75 records from Planktic foraminifera counts of sediment core V26-124. 286 records from (Figure 2) Distribution chart of dinoflagellate cysts of Cretaceous age from ODP Hole 103-638C. 69 records from (Table 3c) Distribution of planktonic foraminiferal tests in sediments from Core NKA-40T. 700 records from (Table 3c) Foraminiferal distribution chart of ODP Hole 122-762C. 6629 records from Benthic biodiversity along the central coast in the Brazilian EEZ (OBIS South America, BRAZIL) (OBIS South America, BRAZIL). 802 records from Biological Collection, National Institute of Oceanography, Goa, India. 33883 records from Joint Nature Conservation Committee - Vegetation surveys of coastal shingle in Great Britain. 4380 records from RMT Trawl catch from the 1980/81 V5 FIBEX voyage (Australian Antarctic Data Centre). 16344 records from Coleccion de sonidos ambientales. 1364 records from Irish Collembola records. 7 records from Calvia explanata sp. n. (Coleoptera: Coccinellidae: Coccinellinae) from the Indian Subcontinent. 205653 records from Inventaire National du Patrimoine Naturel : Oiseaux nicheurs de France. 19 records from Goethe-Hauptschule/Projekt I-10. 66 records from Total living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >30 µm. 9 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, >150 µm. 27 records from Total foraminifera counts of trap L3_92_45. 8 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 1 records from Wirtschaftsgrünland, Intensiv genutze Wiese. 12 records from Nannofossil abundance of Hole 31-299. 12 records from Microplankton abundance at bottle station SEPT-1999-K1. 10 records from A new Neoplatyura Malloch from Finland (Diptera, Keroplatidae). 47 records from Three new Parananochromis species (Teleostei, Cichlidae) from Gabon and Cameroon, Central Africa.. 13325 records from Herbier du Bénin. 209 records from (Appendix A) Palynofacies absoulte abundances of DSDP Hole 38-338. 43 records from Gewässeruntersuchung Grötzinger Baggersee. 25 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >125 µm. 54 records from Plasm bearing foraminifera counts of multinet M21/2_MSN629. 60 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/543-5. 74 records from Faunal assemblage of sediment core TR149-36. 26 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Thinocoridae. 268 records from Geometry of coccolith Coccolithus pelagicus in sediment core PS1113-1. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/553-3. 5538 records from Colección Alberto Tinaut (Formicidae). 45 records from BIRDRACE Ohne Graureiher läuft nix!. 60 records from (Table 5) Quality control of palynoclasts, palynomorphs and microplankton abundances in ODPHole 112-686B. 2577 records from Avifauna de la Isla de Cozumel, Quintana Roo_3. 333 records from (Table 4) Relative abundance of some planktonic foraminifera and fragmentation ratios for ODP Hole 117-728A samples. 4971 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF. 836 records from Visual Plants (144.41.33.158) - Botanical garden, University of Hohenheim, Germany. 4 records from Occurrence of mammalia relicts at site Henauhof NW 2. 3 records from A new species of the Asian catfish genus Pseudolaguvia from Myanmar (Teleostei: Ostariophysi: Siluriformes: Erethistidae).. 10234 records from Collection entomologique Barthélémy. 180 records from Assemblage of living benthic foraminifera in sediment core GeoB3701-1. 149 records from Total foraminifera counts of multinet PO247/2_MSN1372. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_15-CTD175. 1278 records from (Appendix 2-6) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 58-445 in the western Pacific Ocean. 1045745 records from Herbarium of The New York Botanical Garden. 6746 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 14 records from Ostracoda abundance of Hole 44-392A. 2000 records from Shellfish (ASJK_MS). 45 records from Collection Bryozoa - ZIM Hamburg. 1470 records from EDIT - ATBI in Spreewald (Germany). 2025 records from Los crisomélidos del bosque mesófilo de la reserva de la biósfera El Cielo, Gómez Farías, Tamaulipas. 49406 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1985) (AfrOBIS). 13427 records from CNPE/Coleccion Nacional de Peces. 683018 records from The System-wide Information Network for Genetic Resources (SINGER). 48 records from Relative abundance of planktic foraminifera in sediment core K11. 19 records from Antarctic Krill occurrence data from Japanese expeditions. 30 records from A new species of Farlowella Eigenmann and Eigenmann (Siluriformes: Loricariidae), a stickcatfish from Bolivia.. 38 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB01 in the euphotic zone of the Aegean Sea in March 1998. Part 2 - dinoflagellates. 122 records from Occurrence of mammalia relicts at site Hunas. 152 records from Planktic foraminifera abundance of Hole 16-159. 672 records from Range table from planktonic foraminifers in ODP Hole 155-938A. 26079 records from Ohio State University Tetrapod Division - Bird Collection (OSUM). 337366 records from British Lichen Society - BLS Lichen Database: England. 216 records from Range table from benthic foraminifers in ODP Hole 198-1207A. 14 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/090-2. 186 records from (3) Sea Surface Temperature (SST) reconstructed from the percentage of Neogloboquadrina pachyderma sinistral in sediment core MD02-2488 during the period 50-140 ka. 191859 records from herbario. 894 records from CNAN/Arañas sinantrópicas. 6627 records from ATCC Fungi Collection Catalog. 22367 records from Bird Collection. 60 records from (Table 7) Occurrence of selected diatom species in ODP Hole 119-744A. 854 records from (Table T1) Abundance of stratigraphically important planktonic foraminifera in ODP Site 186-1150 sediments. 35 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto11-19. 46 records from Phytoplankton abundance at station DI183_11872#3. 881 records from (Table 2) Planktic foraminifera and their diversity indices of sediment surface samples from the Atlantic Ocean. 5 records from Distribution of Quinqueloculina sp. in sediment core 13200-081. 14 records from Benthic macrofauna abundance of sediment core 12930-081. 129 records from Dinoflagellate cysts from sediment core PS2458-4. 361 records from Water mite collection of Pauli Bagge. 118 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2010. 23 records from Two new species of Pseudolaguvia (Teleostei: Erethistidae) from Bangladesh.. 22 records from Sediment properties of core PLG95B_01BOXG. 350 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 123 records from Birdrace-SportfreundeTriller-Münster. 102 records from BIRDRACE Buteo1DO. 3139 records from (Appendix A) Agglutinated foraminifers in ODP Hole 123-765C. 1660 records from Revisión de la subfamilia Asopinae (Hemiptera-Heteroptera-Pentatomidae) para México. 4 records from Akita Prefectural Museum＋Specimens of Class Maxillopoda of Akita Prefectural Museum. 4641 records from Lepidopterists Society Season Summaries 1973-1997. 1166 records from South Western Pacific Regional OBIS Data Bio Ross Subset (South Western Pac ific OBIS). 1101 records from Relative abundance of ostracods in sediment core Co1202. 122 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB07 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 2240 records from Derbyshire Biological Records Centre - Hemiptera Records 1969 - 2011. 2444 records from (Table 12A) Occurrences of planktonic foraminifers in selected samples of DSDP Holes 90-590 and 90-590A. 205 records from Planktic foraminifera abundance of Hole 29-284A. 994 records from Biological Records In Essex - Bat records for Essex from 1971 - present.. 2 records from Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil.. 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 96 records from Birdrace-federleser-Herford. 68 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-04. 61 records from Total foraminifera counts of multinet M10/2_MSN229. 83 records from Foraminifera species abundances from tow TT011_7-MOC66. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-20-5. 85 records from Epifauna abundance in 2006-10 from an experiment in the Wadden Sea of List, Sylt. 20 records from Heavy minerals of sediment core PL94-60. 1428 records from (Fig. 14) Distribution of dinoflagellate cysts in Early Cretaceous sediments of ODP Hole 103-638B in the North Atlantic. 1 records from Dinoflagellate abundance of Hole 19-183. 92 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 160-969A. 55690 records from The First Atlas of Wintering Birds in Britain and Ireland: 1981/82-1983/84.. 301 records from (Appendix 4, Table 4) Relative abundances of benthic foraminifera in Late Quaternary sediments of core RC09-150 in the southeast Indian Ocean. 162150 records from Ditsong Museum. 1444609 records from Rotherham Biological Records Centre - Rotherham Biological Records Centre - Non-sensitive Records from all taxonomic groups. 1594 records from Musée Vert ornithology collection. 144 records from Ehmkendorf. 3161 records from Census in Agrimey forest reserve (southern Benin). 4 records from "Am Riedert" im Westerzgebirge. 57 records from Royal penguin Eudyptes schlegeli census, Macquarie Island, 1984. 13 records from Nannofossil abundance of Hole 11-103. 34 records from (Table 6B) Distribution of Mesozoic nannoliths at DSDP Hole 43-387. 1000 records from Diplopoda (JJHA-DI). 279 records from (Table 3) Relative abundance of benthic foraminifera in ODP Hole 112-681A. 38 records from (Table 7) Pleistocene nannofossil range chart for ODP Hole 134-832A. 2418 records from Distribution of planktic foraminifera in sediment core GIK23415-9. 167 records from Artenvielfalt auf den Elbwiesen (Dessau). 11 records from Occurrence of mammalia relicts at site l´Abri Caminade-Ouest. 114203 records from UTA Herpetology. 107 records from BIRDRACE Borussia Zippammer. 12 records from (Table 3) Miocene biostratigraphy of the Hemmorian stage in Schleswig-Holstein. 893 records from (Table T1) Neogene dynoflagellate cyst occurrence in ODP Hole 186-1151A sediments. 104431 records from Field Museum of Natural History (Zoology) Fish Collection. 8162 records from CRI - Herbário Pe. Dr. Raulino Reitz. 2 records from Ireneopone gibber (Hym., Formicidae), a new genus and species of myrmicine ant from Mauritius.. 8540 records from Herbarium WRSL, Lichens Collection. 1390 records from Caracterización de avifauna de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 346 records from Benthic foraminifera counts of sediment core GIK23342-6. 207 records from Assemblage of living benthic foraminifera in sediment core GeoB3711-1. 62 records from Total foraminifera counts of multinet M21/4_MSN700. 29 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5112-4. 46 records from Foraminifera species abundances from tow TT007_5-MOC9. 144 records from Abundance of planktic foraminifera at CTD station M39/4_381CTD-34. 11 records from Phytoplankton abundance at station Rigel_2_2005-03 in March 2005, Chipana, Chile. 79 records from Ostracoda abundance of Hole 34-319. 215 records from (App 6) Relative contents of benthic foraminifera species in sediments from Core PS2718-6. 268 records from (Table 5) Relative abundance of benthic foraminifera in ODP Hole 112-686A. 156 records from (Table 2) Distribution of some benthic foraminifera in ODP Hole 108-658A. 40 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE272. 582 records from Bioblitz 2013 Copenhagen Denmark. 37 records from (Table 4) Carbon flux, paleoproductivity, relative abundance of foraminifera on sediment core PS2837-6. 2 records from Nannofossil abundance of Hole 6-50A. 202 records from Dinoflagellate cysts from sediment core PS1295-4. 80 records from (Table 6) Distribution of the large, few-chambered Globigerinelloides species in the Lesches en Diois section. 1513 records from (Table 5) Ranges of benthic foraminifers from the late Oligocene to the early Miocene in ODP Hole 115-714A. 1399 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V22-182. 279 records from Range table from planktonic foraminifers in ODP Hole 175-1077A. 78 records from Microfossil abundance of Hole 21-206. 10 records from Oberservation of birds at station PS14/157 along 49° West. 59928 records from Ifremer BIOCEAN database (Deep Sea Benthic Fauna). 20 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto20-28. 371 records from Fossil occurrence of planktonic foraminifera from IODP Hole 315-C0001H. 3 records from Taxonomy of European Damaeidae (Acari: Oribatida) II. Porobelba weigmanni n. sp. (Oribatida, Damaeidae), from East Slovakia, with comments on other known species of the genus. 36 records from Ecsenius caeruliventris and E. shirleyae, two new species of blenniid fishes from Indonesia, and new distribution records for other species of Ecsenius.. 16 records from Inventarios de Aves de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 520 records from Lepidoptera collection (EL) of the Muséum national d'Histoire naturelle (MNHN - Paris). 114 records from Flora. 63 records from Plasm bearing foraminifera counts of multinet SO118_MSN1266. 38 records from (Table 1) Chiasmolithus species and intermediate forms of ODP Holes 105-647A and 120-748B. 23146 records from BC Coastal Waterbird Survey. 466734 records from ECNASAP - East Coast North America Strategic Assessment (OBIS Canada). 3578 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, 2004-2009 â sensitive records. 61010 records from Fish Collection of Hokkaido University. 10203 records from Coleoptera specimen database of Osaka Museum of Natural History. 1077 records from Percentages of planktonic foraminifera species in sediment core RC24-7. 39 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200320. 5 records from Occurrence of mammalia relicts at site Prekonoska Pecina. 4 records from Occurrence of mammalia relicts at site Grotte Cotencher. 8 records from Planktic foraminifera abundance of Hole 94-611B. 2 records from Abundance of benthos infauna at station GIK23024-1. 14473 records from Entomology at ZMUC, Natural History Musem of Denmark. 1015 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Macuira. 457 records from Microbial Observatory of the Laboratoire Arago. 18 records from A new species of Anabarhynchus (Diptera: Therevidae) from an ocean beach in south east Victoria. 3182 records from Finnish Entomological Database: Heteroptera. 105 records from (Table 1) Occurrence of Early Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 53 records from Alter Lagerplatz und Gartenteich (Dortmund/Hörde). 164 records from Plasm bearing foraminifera counts from M35/1_MSN1064. 56 records from Total foraminifera counts of multinet M21/4_MSN720. 39 records from Sedimentological investigation on core V25-56. 11 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/587-16. 4 records from Sarcodine counts and carbon biomass at station TT008_5-PMOC5. 297 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB01 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 1973 records from Foraminifera abundance of Hole 61-462. 229 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 2066 records from Range table from benthic foraminifers in ODP Hole 159-959D. 4649 records from Inventaire National du Patrimoine Naturel : Flore de Sologne. 277 records from Naturschutzgebiet Börstig bei Hallstadt. 62 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/553-11. 1677 records from Distribution of planktonic foraminifera in DSDP Hole 31-296 (Table III). 6 records from Ostracoda abundance of Hole 13-134. 103 records from Mammals (UWEP-MM). 240 records from (Table 1) Distribution of planktonic foraminifers in ODP Hole 126-787B. 20 records from (Table 6) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-683B. 2820 records from (Figure 6) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-628A. 813 records from Estudio etnobotánico de las malezas útiles presentes en diferentes agroecosistemas en el municipio de Santa María Tecomavaca, Valle de Tehuacán-Cuicatlán, México. 192425 records from Bryophytes of Ireland. 9625 records from Epiphytic Lichens of G. Lettau at the Botanical Museum Berlin-Dahlem. 47 records from Occurrence of mammalia relicts at site Burgtonna. 71 records from Foraminifera abundance of Hole 24-238. 40 records from Range table from planktonic foraminifers in ODP Hole 172-1063A. 4 records from Range table from planktonic foraminifers in ODP Hole 178-1099A. 67 records from Birdrace-Guckers_Offenbach-Offenbach. 2656 records from Swiss Psyllid (Hemiptera) Collections - Basel. 12 records from New data on the European species of three genera Scelionidae (Hymenoptera).. 163 records from Benthic foraminifera and nannofossil abundance of Hole 40-364. 139 records from Siliceous microfossil occurrence, Site 177-1093. 8008 records from Avistajes de espcies de valor especial en áreas protegidas del noreste de Argentina. 1 records from Nouvelles fourmis d'Afrique.. 1 records from On the Australian linyphiid spider Alaxchelicera ordinaria Butler, 1932 (Araneae). 12065 records from Tromsø Museum, Bryophytes. 1150 records from RSPB - Great Yellow Bumblebee sightings data in the UK, 1990 onwards (RSPB, BBCT, HBRG).. 1035 records from National Museum Of Marine Science & Technology. 69 records from Entdeckertour am Muldestausee 1/05. 49 records from Dörnberg. 124 records from Total foraminifera counts of multinet M10/2_MSN232. 7 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_230-23. 4 records from Microzooplankton abundance and biomass at station NBP97-08-16-3. 1811 records from Western Palaearctic Ectoedemia (Zimmermannia) Hering and Ectoedemia Busck s. str. (Lepidoptera: Nepticulidae): five new species and new data on distribution, hostplants and recognition. 4 records from Distribution of Quinqueloculina sp. in sediment core 12930-084. 821 records from Planktic foraminifera counts of sediment core V19-188. 20 records from (Table 2) Stratigraphic occurrence of selected diatom species from DSDP Hole 12-112. 3189 records from Propuesta para la realización de 37 fichas biológicas de las especies de herpetofauna incluidas en la NOM-059 presentes en la Península de Yucatán. 4012 records from Distribution of dinoflagellate cysts in Eocene-Oligocene sediments of ODP Hole 151-913B. 8470 records from (Table 12) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-714A. 3413 records from Planktic foraminifera abundance of Hole 23-219. 1 records from Miriapodi di alcune grotte della Campania. 2 records from Planktic foraminifera abundance of Hole 54-421. 175 records from Range table from benthic foraminifers in ODP Hole 198-1207B. 2737 records from Gunma Museum of Natural History, Molluscan Specimen. 65 records from Sternarchorhynchus curumim (Gymnotiformes: Apteronotidae), a new species of tube-snouted ghost electric knifefish from the lowland Amazon basin, Brazil.. 3 records from Res Ligusticae XXII. Diagnosi di nuove specie di miriapodi cavernicoli. 216 records from (Table A2) Stratigraphic distribution of major planktic foraminifer species of ODP Hole 198-1210A. 3 records from On two Italian Lithobius species described by Silvestri, with taxonomic notes on the genus Eupolybothrus Verhoeff (Chilopoda, Lithobiida). 11 records from A new species of Hemigrammus Gill, 1858 (Characiformes: Characidae) from Rio Caura, Venezuela.. 82 records from Plasm bearing foraminifera counts from M35/1_MSN1050. 31 records from Planktic foraminifera of sediment core GeoB1406-4. 213 records from Coccoliths in sediment core PS1113-1. 19 records from Meiofauna abundance in sediment core 12930-036. 2208 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B (Table 1). 844 records from (Table 2) Relative abundance of 13 species of planktonic foraminifers of sediment core GIK17938-2. 1833 records from DSMZ Fungi. 14 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB04 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 777 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 6 records from Pseudogramma xanthum, a new replacement name for a serranid fish from the subtropical South Pacific Ocean with description of the species.. 18970 records from Cowan Tetrapod Collection - Birds. 27940 records from HAS - Herbário Alarich Rudolf Holger Schultz. 62283 records from PRECIS (KwaZulu-Natal Herbarium). 92 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 7 records from Distribution of planktic foraminifera of sediment core GIK23342-6 at stadium 5.5. 4 records from Trap data WR2, 1648 m. 6 records from Microzooplankton abundance and biomass at station TT043_7-20. 5037 records from Estudios bióticos: plantas, edafofauna epígea, anfibios y aves en los complejos de páramos los Nevados y Chilí-Barragán. 159 records from Phytoplankton abundance at station CD47_0606C#7. 77 records from Distribution of planktonic foraminifera of sediment core SH1972_1. 9 records from A new species of Pseudobagrus (Teleostei: Siluriformes: Bagridae) from southern China.. 201 records from (Table 2) Relative abundances of calcareous nannofossils in ODP Hole 120-748A. 34 records from (Table 6) Temporal variations of relative abundance of dead cells (in detritus, conglomerates and associated with Probocsia alata) of total number of living and dead cells of Emiliania huxleyi at Stations AH-2001-B3 and AH-2001-B3A. 14 records from R. Curry Collection. 441 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 321 records from John Muir Trust - Plants and Bryophytes recorded on Schiehallion 25-30 June 2000. 637398 records from Données ONF Faune-Flore-FOnge. 151010 records from Marie-Victorin Herbarium (MT). 134 records from Birdrace-Team_Havelland-Havelland. 1666 records from Occurrence of planktic foraminifera in Pliocene to Holocene sediments of DSDP Hole 81-552A in the North Atlantic (Appendix 2). 500 records from Plant (HBBG-PL). 399 records from CECT Spanish Type Culture Collection(Fungi). 71 records from Occurrence of mammalia relicts at site Teufelsbrücke. 2353 records from Relative abunances of benthic foraminifera in Late Oligocene to Miocene sediments of ODP Hole 121-757B from the southeastern Indian Ocean (Appendix Table 1). 13382 records from Herbarium specimens, Harmas J.H. Fabre (FABR - Sérignan-du-Comtat) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from Arthropoden aus südostalpinen Höhlen.. 8 records from Phytoplankton abundance at station Casma_2003-06-24_1, Casma, Peru. 112 records from Werl macht sich auf die Suche. 177 records from BIRDRACE Die Kielbris. 4 records from Nannofossil abundance of Hole 8-75. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/092-3. 78 records from Mammals (GNHM-MM). 2109 records from Planktonic foraminiferal abundances, and sea surface and export production reconstructions of sediment core SU92-03. 720 records from (Table 5) Distribution of planktonic foraminifers in ODP Hole 126-793A. 162 records from Bases de datos de Tanaidaceos (Crustacea: Peracarida) del Mar Caribe mexicano. 1011 records from Biodiversidad fitoplanctónica de cenotes: Patrones espaciales y temporales. 80 records from Collection Copepoda - SMF. 86154 records from Naturalis Biodiversity Center (NL) - Coleoptera. 4 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Frank Haubrich. 501 records from Planktic foraminifera assemblage in sediment core GIK17045-3. 1 records from Arthropoden aus südostalpinen Höhlen.. 355 records from Tag der Artenvielfalt. 11 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR50. 508 records from Planktic foraminifera abundance of Hole 23-222. 17720 records from Collection Polychaeta SMF. 4 records from A new and presumably extinct species of Ptychochromoides (Teleostei: Perciformes: Cichlidae) from central Madagascar.. 5148 records from Colección de Reptiles - Museo de Herpetología de la Universidad de Antioquia. 1168 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 7032 records from EAN - Herbário Jaime Coelho de Moraes. 470 records from Spiders_of_French_Guiana. 40 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 174-1072A. 271 records from kisti_microb. 20755 records from pins. 2356 records from Naturalis National Natural History Museum (NL) – Aves_Types. 367 records from Clyde River Foundation - Twaite Shad (Alosa fallax) distribution for Scotland, historical to present. 1 records from Oppiella signata, eine neue Art der Familie Oppiidae aus dem Osterzgebirge (Acari, Oribatei). 68 records from Late Pleistocene planktonic foraminifera of Hole 302-M0004C (Addendum 1). 464 records from Lepidoptera collection, NTNU, Trondheim. 24 records from 10) SST, IRD and benthic foraminiferal d18O data from the Norwegian Sea core MD95-2010: revised chronology for the Last Interglacial (period 134-110 ka). 4 records from Sächsische Schweiz (Wehlener Gebiet). 234 records from Wiesen-Wälder-Wasser um Dansenberg, Biosphärenreservat Pfälzerwald. 126 records from Total foraminifera counts of multinet PO231/3_MSN1336. 120 records from Total foraminifera counts of multinet PO247/2_MSN1387. 184 records from Abundance of calcareous dinoflagellates of sediment core GeoB3603-2. 753 records from Dinoflagellates (organic) in surface sediments of the South Atlantic. 2 records from Smear slide analysis of sediment core GeoB7427-2. 2 records from Nannofossil abundance of Hole 74-526. 21 records from Nannofossil abundance of Hole 19-192. 1336 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 127 records from BIRDRACE Southernmost Lakers. 1808 records from Ant'Phipoda Database (New records). 4 records from Herpetology Collection. 94 records from Landschaftsschutzgebiet Buchhorst 4. 19 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 251744 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 1 records from Karpfenteich, Klasse 6d. 10 records from Concentration of siliceous microplankton in surface sediments, size fraction 20-40 µm. 6188 records from (Figure 1) Range chart of planktonic foraminiferal species at ODP Hole 107-654A. 874 records from Flora acuática de Querétaro. 603 records from Polish Arctic Marine Programme (EurOBIS). 1086 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC17-98. 42 records from (Table 2) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-543. 1 records from Zetes longiusculus. 372 records from El efecto de la variación ambiental en la diversificación de anfibios y la prevalencia de su patógeno mortal: Un transecto por los humedales desde el Magdalena Medio hasta la Orinoquía. 2300 records from Botanical Society of the British Isles - Demonstration set of data downloaded from the BSBI threatened plant database. 25 records from Phytoplankton abundance at station Sechin_2003-11-25_2, Casma, Peru. 609 records from Herbier L. Mulon (BOUM). 32356 records from Actualización de la base de datos del Atlas Mastozoológico de México. 546 records from 20 Jahre Naturschutzgebiet Dreienberg. 15575 records from (Appendix A) Planktonic foraminifer abundance and ranges of ODP Hole 165-999A sediments. 9 records from "Ach, du dicke Eiche", Wald an der Oste-Grundschule Heeslingen. 108 records from (Table 7) Planktonic foraminifera species in bottom sediments of Core ML5_348, North Atlantic. 269 records from BIRDRACE speedbirder. 84 records from BIRDRACE Vogelscheuchen. 2 records from Planktic foraminifera counts of multinet PS2616-5. 15 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2177-3. 456 records from Øvre Heimdalsvatn, Radiocaesium (Cs-137) monitored annually in brown trout (Salmo trutta). 16 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT008_5-CTD42. 52359 records from Iziko. 34 records from Two new species of Pseudecheneis, rheophilic catfishes (Teleostei: Sisoridae) from Nepal.. 13884 records from (Figure 3) Range chart of dinocysts of ODP Hole 104-643A. 24286 records from Ross A. Layberry Observations. 9858 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 9 records from Microplankton abundance at bottle station SEPT-1999-K8. 21 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100260. 45 records from Occurrence of mammalia relicts at site Erdhöhle. 535 records from Benthic foraminifera abundance of Hole 73-522. 709 records from Range table from benthic foraminifers in ODP Hole 139-857A. 14 records from Collection Pantopoda SMF. 228 records from MNA (Section of Genoa) and NIWA Invertebrate Collection - Ross Sea Tanaidacea. 101 records from (Table S1d) Measured tomographic parameters for Oridorsalis umbonatus during ETM-2 for ODP Holes 208-1263C and 208-1262A. 6328 records from Naturalis National Natural History Museum (NL) – Indo-Pacific Plio-Pleistocene fossils. 2458 records from Colección de Ictiología. 76124 records from Lichen field notes, Oslo (O). 88018 records from NINA Vanndata øvrige arter. 1 records from Oribates angulatus. 1 records from Microzooplankton abundance and biomass at station TT050_25-4. 26 records from Nannofossil abundance of Hole 37-332A. 418 records from Fossil (GNHM-FO). 13 records from (Table 14) Distribution of Pleistocene to late Pliocene nannofossils in ODP Hole 108-668A. 11 records from (Table 4a) Abundances of Globorotalia menardii in sediment core INMD-097BX. 3734 records from Anfibios, reptiles y mamíferos del corredor biológico del norte de Yucatán depositados en las colecciones de la Escuela Nacional de Ciencias Biológicas. 4 records from Description of lithologic section units of IODP Hole 325-M0034A. 13 records from Planktic foraminifera abundance of Hole 60-460A. 2 records from Pollen analysis of sediment profile KR0 from Kreutzsee. 6081 records from UNR Herpetology. 28 records from Two new species of Pamphobeteus Pocock 1901 (Araneae: Mygalomorphae: Theraphosidae) from Brazil, with a new type of stridulatory organ. 113 records from Total foraminifera counts of multinet M21/2_MSN627. 2 records from Microzooplankton abundance and biomass at station TT050_11-4. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-01-10. 4 records from Nannofossil abundance of Hole 31-293. 52 records from Meiofauna abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas ?. 935041 records from NatureServe Network Species Occurrence Data. 31 records from Planktic foraminifera assemblage in sediment core GIK17732-1. 3 records from Planktic foraminifera abundance of Hole 17-166. 37 records from Range table from benthic foraminifers in ODP Hole 182-1128D. 13909 records from Albany Museum. 16866 records from Gravel Master Thesis / Chubut, Argentina. 438 records from (Table 3) Distribution of calcareous nannofossils from selected samples of ODP Hole 107-653A. 243 records from (Table 1) Oligocene benthic foraminifers abundance in ODP Hole 124-767B. 245 records from Echuya Survey 2012. 337 records from Zooplankton of the Eastern South Pacific, Universidad de Guayaquil, Ecuador (OBIS South America, SOUTH PACIFIC NODE). 90 records from Planktic foraminifera abundance of Hole 24-233A. 24 records from Range table from benthic foraminifers in ODP Hole 192-1185B. 1 records from Siphonaptera fossil - SMNG. 107 records from RSPB - Crested tit wintering survey in the UK, 1992-1995 (RSPB). 1 records from Fourmis récoltées à Madagascar, par le Dr. Conrad Keller.. 1391 records from Lichen herbarium, NMBU. 2963 records from MfN - Diptera Collection. 336 records from (Table T1) Calcareous nannofossil abundance estimates of ODP Hole 210-1276A.. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 52 records from Isotope tracer experiment: meiofauna counts. 455 records from (Table T2) Calcareous nannofossil abundance across the Oligocene/Miocene boundary of ODP Hole 189-1168A sediments. 1243 records from Crustacea ZMK. 14605 records from DMNS Mammal Collection (Arctos). 81 records from Birdrace-Die_Ornithomaten-Herford. 115 records from Plasm bearing foraminifera counts of multinet M21/1_MSN614. 140 records from Dinoflagellate cysts counted on two fractions of surface sediment samples from stations A-9 to A-39. 98 records from Colección Nacional de Heliconias. 1 records from Nothrus biciliatus. 20 records from Hübsche Kröten, Wetterfrösche und andere Froschnaturen. 287 records from BIRDRACE Pody und Co. 88 records from Plasm bearing foraminifera counts of multinet M21/2_MSN627. 13 records from Content of coarse fraction and G. menardii in sediment corev V25-49. 3 records from Sarcodine counts and carbon biomass at station TT011_4-CTD46. 8 records from Zoobenthos in surface sediments in the Yalta Bay. 22 records from Coleoptera identified from the Hornchurch Marshes site, Dagenham, London. 2 records from Nannofossil abundance of Hole 66-489A. 16 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/012-5. 52 records from Nannofossil abundance in sediment core PS1297-4. 67 records from (Table 2) Distribution of ostracodes in ODP Hole 107-650A. 1323 records from Estación Experimental de Zonas Áridas (CSIC), Almería: EEZA-Ungulados. 1380 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 126-790. 35 records from Akita Prefectural Museum＋Reptiles Specimens of Akita Prefectural Museum. 7881 records from Algaterra Types. 33 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, 30-63 µm fraction. 43 records from Assemblage of living benthic foraminifera in sediment core CD145_55808#3, 63-150 µm. 16 records from Phytoplankton abundance at station Sechin_2003-10-03_2, Casma, Peru. 14 records from Phytoplankton abundance at station Sechin_2003-12-28_1, Casma, Peru. 78 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1a. 68 records from (Table 3) Macro- and meiofaunal species abundance in box core samples from the North Pacific Ocean. 322 records from Nannofossil abundance of Hole 15-147. 13 records from Benthic macrofauna abundance of sediment core 13200-081. 230 records from (Table 1) Relative abundance of benthic foraminifera in ODP Hole 112-679D. 84 records from Seawater carbonate chemistry and processes during experiments with phytoplankton Emiliania huxleyi (strain Bergen 2005), 2010. 199 records from La fauna de Melolonthidae, Cerambycidae y Elateridae (Insecta: Coleoptera) de la reserva de la biósfera El Triunfo, Chiapas. 1612 records from Plant Specimens of Wakayama Prefectural Museum of Natural History. 420 records from (Table 4) Relative abundances of planktonic foraminifera in Pliocene sediments of ODP Site 161-975 in the Mediterranean Sea. 160 records from Schulgelände Schule auf der Aue, Münster. 37 records from Planktic foraminifera abundance of Hole 29-279. 196 records from Range table from planktonic foraminifers in ODP Hole 162-986D. 767 records from Phytoplankton abundance in surface water in February 1998, Paita, Peru. 181724 records from ArtenFinder. 9396 records from RSPB - White-tailed eagle reintroduction in Scotland - Sightings data (RSPB/SNH). 48 records from Pollen counts of sediment core GeoB9503-5. 25 records from Heavy minerals of sediment core PL94-08. 60 records from (Table 2) Quantitative parameters of the Emiliania huxleyi population at the section along 70 m isobath carried out on 26 and 27 August 2001. 750 records from (Table 20) Benthic foraminifera in early Miocene sediments of DSDP Hole 90-594. 441 records from Planktic foraminifera distribution of sediment core 75KS76. 2504 records from Collections data on ecology of bottom animal of the Southern ocean. 14 records from Range table from planktonic foraminifers in ODP Hole 143-865B. 63 records from Range table from benthic foraminifers in ODP Hole 172-1062B. 465 records from Fish catch from 1996/97 Voyage 2 WASTE (WOCE Antarctic Southern Transect Expedition). 187 records from Taxonomic revision of the Pachycondyla apicalis species complex (Hymenoptera: Formicidae).. 113482 records from KUBI Ornithology Collection. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 1 records from Streuobstwiese Alt Necheln. 159 records from Plasm bearing foraminifera counts of multinet M21/1_MSN606. 75 records from Foraminifera species abundances from tow TT007_8-MOC15. 785 records from Faunal distribution of the most important planktic foraminiferal species in the investigated surface sediment samples from the Chilean continental slope between 23°S and 44°S. 14 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/323-1. 4 records from Nannofossil abundance of Hole 29-284A. 48 records from Planktic foraminifera abundance of Hole 6-47. 16282 records from Atlas der Raubfliegen Deutschlands - database. 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 9858 records from Planktic foraminifera distribution on sediment core GIK17957-2. 16 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 1322 records from Planktic foraminifera abundance of Hole 29-284. 269 records from Range table from planktonic foraminifers in ODP Hole 182-1126C. 1578995 records from Inventaire National du Patrimoine Naturel : Flore Franco-Belge. 5316 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 131 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Hole 182-1127B. 7 records from Solifugae Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 12509 records from The Bat Conservation Trust - Hibernation Survey. 360 records from Küstenschutzwald. 44 records from "Schlechteberg" Ebersbach/Sa.. 129 records from Total foraminifera counts of multinet M12/3_MSN561. 98 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1381. 1371 records from (Appendix 2-7) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 59-451 in the western Pacific Ocean. 82 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_6-CTD67. 15 records from Meiofauna abundance in sediment core 54301-016. 138 records from (Table 2a) Species composition of planktonic foraminiferas in bottom sediments from Core AK6-434-1. 214 records from Planktic foraminifera counts of sediment core V27-86. 157 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera of surface sediment off Morocco (Table 6). 19 records from (Table S2) Calcareous nannoplankton morphometric analyses performed of DSDP Hole 62-463 samples. 16 records from A review of the gobiid genus Akko (Teleostei: Gobiidae) with description of a new species.. 2419291 records from British Bryological Society - Bryophyte data for Great Britain from the British Bryological Society held by BRC. 5 records from Ventichthys biospeedoi n. gen. et sp. (Teleostei, Ophidiidae) from a hydrothermal vent in the South East Pacific.. 27290 records from Bird Monitoring Data. 291 records from Benthic foraminifera counts of sediment core GIK17730-4. 1 records from Microplankton counts and carbon biomass at station TT011_3-CTD33. 8 records from Aktion des Romain-Rolland-Gymnasiums. 32466 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 2005) (AfrOBIS). 42 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Florian Werner. 91 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 56 records from Range table from planktonic foraminifers in ODP Hole 167-1010C. 1803 records from Vertebrate specimens of Jyväskylä University Museum. 3550 records from Herbarium specimens of Institut Scientifique Mohamed V university (RAB). 5 records from (Table T9) Calcareous nannofossil stratigraphy of ODP Hole 198-1211C. 51499 records from NRM-Fishes. 327284 records from Fungi (S). 51 records from Packer Collection / Xenochilicola bees, Chile. 36459 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 134 records from Planktic foraminifera counts of sediment core V19-202. 4778 records from SO-Polylist. 3 records from Meiofaunal abundance, biomass, taxon richness and indices of nematode diversity of samples from the Santa Maria di Leuca Bank (southern Adriatic margin). 568 records from Planktic foraminifera assemblage in sediment core SU92-21. 171988 records from Tromsø Museum, Vascular plants. 10 records from Ecsenius niue, new species of blenniid fish, and new distribution records for other species in the Opsifrontalis species group.. 15902 records from Field Museum of Natural History (Botany) - Historical Photographs of Type Specimens from Berlin (B). 3 records from Analyses of the recent components of sediment core PS1010-1. 81 records from Range table from planktonic foraminifers in ODP Hole 180-1109D. 358 records from (Appendix 3, Table 4) Relative abundances of benthic foraminifera in Late Quaternary sediments of core BMR96GC21 in the southeast Indian Ocean. 2330 records from Seaweed (Plantae) Collection of the Seto Marine Biological Laboratory, Kyoto University. 144765 records from Invertebrates Collection of the Swedish Museum of Natural History. 54 records from Three new species of Gastromyzon (Teleostei: Balitoridae) from southern Sarawak.. 134 records from Total foraminifera counts from M35/1_MSN1046. 7 records from Microzooplankton abundance and biomass at station NBP97-08-29-1. 46 records from Liether Park (LMS), 5a. 1649 records from MfN - Trace fossils. 40 records from Nannofossil abundance of Hole 21-205. 39650 records from (Table T1) Miocene planktonic foraminiferal stratigraphy of ODP Hole 184-1148A. 153299 records from Insekten Sachsen. 1 records from Damaeus torvus. 91 records from (Table 1) Distribution of Lower Cretaceous calcareous nannofossils in ODP Hole 123-765C. 13842 records from BCCM/LMG - Laboratory of Microbiology Gent Bacteria Collection. 205599 records from CABI Bioscience Fungus Collection. 1614 records from New Brunswick Museum Collection. 6 records from Planktic foraminifera abundance of Hole 23-226. 37 records from Range table from benthic foraminifers in ODP Hole 146-891A. 850 records from RSPB - Crossbills, Distribution survey in Great Britain, 1995-2005 (RSPB). 1851 records from (Figure 2) Foraminifera in lower to middle Albian sediments of DSDP Hole 80-549. 64 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 122 records from Total foraminifera counts of multinet M21/2_MSN651. 2 records from Nannofossil abundance of Hole 1-4. 7 records from Nannofossil abundance of Hole 49-409. 8 records from Diatom abundance measured on water bottle samples at station PS58/091-4. 17 records from Taxonomy and distribution of the ant Cataglyphis setipes (Hymenoptera: Formicidae). 98 records from Occurrence of mammalia relicts at site Felsställe. 632 records from Dinoflagellate abundance in sediment core JM06-WP-04-MCB. 39 records from A review of the Malagasy Pachypanchax (Teleostei: Cyprinodontiformes, Aplocheilidae), with descriptions of four new species.. 191 records from Herpetofauna laguna El Tinije. 68 records from (Table 8) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-851B. 26835 records from Herbario Pontificia Universidad Javeriana. 111 records from Birdrace-Uhulogen-Lippe. 120 records from Birdrace-The_early-Birds-Minden/Lübbecke. 11 records from Vögel im Garten Kindergarten Zaisertshofen. 146 records from Total foraminifera counts from multinet M31/2_MSN891. 113 records from Plasm bearing foraminifera counts from M35/1_MSN1062. 193 records from Total foraminifera counts of multinet M21/3_MSN663. 145 records from Ostracoda abundance in DSDP Leg 87 holes. 765 records from Colección de peces marinos del mar argentino y aguas adyacentes del INIDEP. 3666 records from (Table 5) Stratigraphic ranges of selected Oligocene to earliest Miocene planktonic foraminifers in ODP Hole 115-709A. 1035 records from Estudio de la diversidad florística en la región de la Chinantla, Sierra Norte de Oaxaca. 342 records from (Table 1) Dinoflagellate cysts and acritarchs in upper Pliocene and Pleistocene sediments from ODP Hole 151-911A. 1184 records from iziko South African Museum - Marine Mammal Collection (AfrOBIS). 73821 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1986) (AfrOBIS). 5507 records from MAR - Herbário do Maranhão. 66 records from Occurrence of mammalia relicts at site Malerfels_I. 542 records from Planktic foraminifera abundance of Hole 18-175. 135656 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, 2004-2009. 384 records from Phytoplankton abundance in surface water in June 1997, Callao, Peru. 25727 records from Irish National Badger Sett Database. 116772 records from Plant Specimen from Herbarium (IBK) in China, Guangxi Institute of Botany, Chinese Academy of Sciences. 171 records from Hormigas de hojarasca asociadas a fragmentos de bosque y cafetales de la zona cafetera de Cundinamarca. 184 records from (Table 2b) Biomass of macrobenthos species in samples from Cruise AMK54 stations in the Novaya Zemlya Trough. 7 records from Additions to the myxobiota of the Åland Islands. 1322 records from Targeting a portion of central European spider diversity for permanent preservation. 3637 records from Lepidoptera collection of NW Europe. 3 records from (Table 5) Organic matter contents and paleoproductivities at DSDP Site 75-532. 99454 records from ICN - Herbário do Instituto de Ciências Naturais. 960 records from (Table 4) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Site 167-1013 sediments. 1894 records from Aves Playeras y Otras Aves Asociadas a Arrozales en los Departamentos de Casanare y Meta en 2009 - 2010. 11 records from Umgebung Jugendherberge Clausthal, Klasse 8d. 166 records from Plasm bearing foraminifera counts of multinet M21/1_MSN610. 40 records from (Supplementary Table 2) Estimates of bottom-water oxygenation at site GeoB11185-1. 68 records from Microzooplankton abundance measured on water bottle samples at station PS58/088-4. 1584 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 55 records from (Table 2c) Species compositioon of planktonic foraminiferas in bottom sediments from Core ML1_66. 2794 records from Diversidad bentónica de la laguna Celestún, Yucatán. 1154 records from Collection Plecoptera - SMF. 69009 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1989) (AfrOBIS). 3 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Frederike Proewe. 677 records from Insect colletion. 2320 records from Planktic foraminifera assemblage of sediment core ELT49.018-PC. 1073 records from Relative abundance of planktic foraminifera in sediment core RC17-69. 28 records from (Appendix A3) Paragloborotalia morphometric and coiling data from Oligocene sediments of ODP Site 199-1218 in the equatorial Pacific. 459 records from NSG Karwendel. 13894 records from TEPB - Herbário Graziela Barroso. 9256 records from Hemiptera collection (EH) of the Muséum national d'Histoire naturelle (MNHN - Paris). 77605 records from MGC Herbarium of University of Malaga (Spain): MGC-Cormof dataset. 2312 records from Mycological collection of the National Museum. 13 records from Planktic foraminifera counts of multinet PS31/002. 3 records from Sarcodine counts and carbon biomass at station TT007_7-CTD76. 10 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2159-3. 7 records from Pseudomystus stenogrammus, a new species of bagrid catfish from Borneo (Teleostei, Bagridae).. 55 records from Seeufer ehem. BUGA-Gelände. 3347 records from Mammal and Fish speciemens of Kumamoto City Museum. 78 records from Nannofossil abundance of Hole 27-262. 142 records from (Appendix C) Average nannofossil abundances in mid-Pliocene sediments from the equatorial Atlantic. 11 records from Benthic macrofauna abundance of sediment core 13200-017. 1584 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 112-681. 407 records from Myriapoda - SMF. 2524 records from (Table 13) Ranges of benthic foraminifers through the early to middle Miocene in ODP Hole 115-715A. 1395 records from Birds - Wild Birds (KIDR-BI). 66 records from Planktic foraminifera assemblage in sediment core GeoB1113-4. 2 records from Schistura papulifera, a new species of cave loach from Meghalaya, India (Teleostei: Balitoridae).. 333 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Charadriidae. 51 records from University of Amsterdam (NL) - Páramo Vegetation Research, Bordoncillo - Nariño, Colombia. 154 records from Dermaptera in the icipe collection. 6 records from (Table 1d) Principal petrographic characteristics and K-Ar isotope-geochronological data on samples from the Late Neopleistocene - Holocene activity phase of the Keli Volcanic Highland. 677 records from Meiofauna abundance of central Mediterranean Sea mud volcano sediments. 178 records from RSPB - Corn bunting surveys on the Western Isles. 1376 records from (Appendix B) Abundance of dinoflagellates in sediment core MD01-2378. 929 records from Flora acuática vascular de las regiones hidrológicas R66 (Lagos Cráter del Nevado de Toluca) y R67 (Río Amacuzac-Lagunas de Zempoala), México. 9322 records from (Figure 3) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548A. 143811 records from DFO Maritimes Research Vessel Trawl Surveys Fish Observations (OBIS Canada). 2310 records from (Table 15A) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-593. 3952 records from Range table from benthic foraminifers in ODP Hole 159-962D. 1905 records from BioGIS - Reptiles - INPA database. 1641 records from NCSM PaleoBotany Collection. 36 records from Selz (Ingelheim am Rhein). 124 records from Total foraminifera counts of multinet M21/1_MSN620. 1 records from Microplankton counts and carbon biomass at station TT008_6-CTD64. 140 records from Distribution of planktonic foraminifera of sediment core SH1972_17. 18 records from (Table 1.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Polarstern cruise ANT-XXIII/7. 4500 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene of ODP Hole 105-645E (Table 1). 32 records from (Table 4) Carbonate and washed residue weight percentages in ODP Hole 121-758B. 2760 records from RMT Trawl catch from the 1995/96 V4 BROKE voyage. 3477 records from Aves laguna El Tinije. 7 records from Analyses of the recent components of sediment core PS1402-2. 380 records from Artenvielfalt der Nordsee - Helgoland. 20 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB06 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 1092 records from Range table from planktonic foraminifers in ODP Hole 155-936A. 745 records from Gunma Museum of Natural History, Mammal Specimen. 1 records from Scutellista caerulea (Fonscolombe, 1832) (Hymenoptera: Pteromalidae), new to New Zealand for the second time!. 58 records from A revision the Australian species of the ant genus Myrmecina (Hymenoptera: Formicidae).. 6 records from Fließgewässeruntersuchung am Haselbach. 7380 records from University of Ghent - Zoology Museum - Invertebratacollectie. 30 records from Microzooplankton abundance measured on water bottle samples at station PS65/553-3. 16 records from Nannofossil abundance of Hole 24-235. 73 records from Macrofauna abundance in surface sediment sampled during cruise DI222/2. 6 records from Relationships of the New World cichlid genus Hypsophrys Agassiz 1859 (Teleostei: Cichlidae), with diagnoses for the genus and its species.. 53 records from Planktic foraminifera assemblage in sediment core GIK23041-1. 275 records from Wald und Wiese am Buchwald. 24 records from Range table from planktonic foraminifers in ODP Hole 170-1039A. 19 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 1 records from Damaeus auritus. 2 records from Lubbockichthys myersi, a new species of dottyback fish from Guam (Pseudochromidae: Pseudoplesiopinae).. 56 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 30-63 µm fraction. 152 records from Planktic foraminifera counts at CTD station M39/4_402CTD-55. 22 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/043-2. 433 records from Caracterización de las coberturas vegetales en el gradiente altitudinal Páramo-Bosque en los complejos de Páramo de Guerrero y Altiplano Cundi-boyacense. 968 records from (Table T17) Planktonic foraminifera stratigraphy of ODP Hole 198-1211A, Zones P14-P18. 5920 records from Alterra (NL) - Microarthropods inventories by Henk Siepel on various locations. 33070 records from CSIRO Ichthyology provider for OZCAM. 58 records from Schulhof der Astrid-Lindgren-Schule und Umgebung (Elmshorn). 34 records from Numbers and dry weights of meiobenthos taxa in surface sediments at Fladen Ground station 1, North Sea (Table 6). 16 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/313-1. 17 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/321-1. 448 records from Geometry of coccolith Gephyrocapsa in sediment core GIK23062-1. 2 records from Nannofossil abundance of Hole 3-17A. 390 records from (Table 3) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the upper part of the Cismon core. 408 records from Visual Plants (144.41.33.158) - Private collection of Rainer Bussmann. 718 records from Zukünftiges NSG Höftland/Bockholmwik. 90 records from Range table from benthic foraminifers in ODP Hole 146-889B. 12768 records from (Table 4) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-872C. 764 records from BioGIS - Fish - INPA database. 4779 records from (Table S1) Benthic foraminifera of ODP Holes 199-1218A and 199-1219A. 279 records from Koleopterologen am Bausenberg. 28 records from Smear slide analysis on sediment core GeoB4217-5. 129 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 79186 records from All Ireland Non-Marine Molluscan Database. 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-14, >125 µm fraction. 918 records from (Fig. 4) Assemblage of benthic foraminifera in sediment core GeoB6725-1. 20 records from Assemblage of living benthic foraminifera in sediment core SO117_MC469, >125 µm fraction. 153 records from Distribution of planktic foraminifera (125-250 µm) of sediment core PS1909-2. 1309 records from Mongolian Plant (MMNH-PL). 296 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE233. 316 records from (Table 2) Distribution of planktonic foraminiferal tests in sediments from Core ML7_475. 2784 records from (Figure 3) Distribution of benthic foraminifers in the Albian of DSDP Hole 71-511. 154124 records from Arizona State University Lichen Collection. 11 records from Occurrence of mammalia relicts at site Rotselaar. 1042 records from Planktic foraminifera abundance of Hole 37-333. 122 records from VFD-BW, Linzgau: Pferdeweiden Neuweiler Hof. 3 records from Nouvelles fourmis de Madagascar.. 424 records from Taxonomic Revision of the Ant-Acacias (Fabaceae, Mimosoideae, Acacia, Series Gummiferae) of the New World. 122 records from A contribution to the study of the Lower Volga center of scarab beetle diversity in Russia: checklist of the tribe Aphodiini (Coleoptera, Scarabaeidae) of Dosang environs. 33 records from Description of two new species of Avicularia Lamarck 1818 and redescription of Avicularia diversipes (C. L. Koch 1842) (Araneae, Theraphosidae, Aviculariinae) - three possibly threatened Brazilian species. 6 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cariamidae. 459 records from Colección de Entomología - Coleoptera - Chrysomeloidea. 79 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1375. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD85. 14 records from Microzooplankton abundance and biomass at station NBP97-03-11-1. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-18-5. 9 records from Abundance of radiolaria at station UT99-24-1. 2 records from Wie viel Natur gibt es im Park?. 8 records from Nannofossil abundance of Hole 49-412A. 48 records from Nannofossil abundance in sediment core PS1314-4. 31 records from Pollen profile V and Ausfluss at Krumbach, Germany. 20 records from (Table 2) Abundance and biomass of the main microplankton biota components in the Murmansk coastal pelagic zone in March 1998. 56081 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Herbario COFC). Facultad de Ciencias. Universidad de Córdoba. 96489 records from Colección Ornitológica del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 29362 records from Highland Biological Recording Group - HBRG Vertebrates (not Badger) Dataset. 12 records from Microplankton abundance at bottle station SEPT-1999-K4. 14 records from Occurrence of mammalia relicts at site Crumstadt 1. 15 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 1256 records from Foraminifera abundance of Hole 64-481. 7 records from Range table from planktonic foraminifers in ODP Hole 169-1038H. 22998 records from BOTU - Herbário Irina Delanova Gemtchújnicov. 1769 records from Distribution of benthic foraminifera in DSDP Hole 24-238 in the Central Indian Ocean (Appendix A). 302 records from Kohlstattbrunnental. 1099940 records from DOF 2001-2006. 494248 records from British Lichen Society - BLS Mapping Scheme dataset, 1750-2009. 663 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Lacewings and Allies (BNHS) - 1942-2009. 45 records from Range table from planktonic foraminifers in ODP Hole 182-1130C. 4132 records from (Table 2) Calcareous nannofossil abundance in ODP Hole 164-994C sediments. 19 records from Three new species of Microbrotula (Teleostei: Ophidiiformes: Bythitidae) from the Indo-West Pacific.. 28 records from (Table 2) Oligocene to Pliocene nannofossil range chart for ODP Hole 134-828A. 12 records from Abundance of radiolaria at station LV28-44-1. 219 records from (Table 2) Stratigraphic distribution of planktonic foraminifera from the middle Miocene to upper Miocene in ODP Hole 134-832B. 13 records from Benthic macrofauna abundance of sediment core 13200-008. 950 records from (Table 9) Distribution of planktonic foraminifera in the early Pliocene to Holocene section of ODP Hole 149-900A. 2178 records from Flora exsiccata Bavarica. 185 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 11 records from Oberservation of birds at station PS14/145 along 49° West. 7360 records from (Figure 6) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-550. 5263 records from Colección Herpetológica (anfibios) de la Universidad Industrial de Santander. 500808 records from Neptune Deep-Sea Microfossil Occurrence Database. 17 records from Meiofauna abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 258 records from BIRDRACE Raumpatrouille Oriolus. 933 records from (Table T3) Planktonic foraminifera abundance of ODP Site 170-1041 sediments. 4318 records from Diptera Collection of Museum and Institute of Zoology PAS. 25 records from (Table 1) Osmium isotope ratios and Re-Os element content in bulk sediments of ODP Hole 121-758A. 17 records from (Table A) Fauna associated with Bathymodiolus azoricus mussel beds within the Menez Gwen hydrothermal field, Mid-Atlantic Ridge. 1 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 161 records from Schulgelände Paul-Gerhardt-Schule-Dassel. 1 records from Opamyrma hungvuong, a new genus and species of ant related to Apomyrma (Hymenoptera: Formicidae: Amblyoponinae). 22 records from Abundance of Globorotalia menardii of sediment core GeoB2822-2. 383 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 177 records from Donauinsel des BN bei Entau. 4 records from MfN - Fossil vertebrates II. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_5-CTD56. 2 records from Nannofossil abundance of Hole 14-144A. 19 records from (Table 2) Range chart of calcareous nannofossils from Maud Rise sediment cores. 1638 records from (Table 1) Relative abundances of benthonic foraminifera in ODP Site 116-717. 146624 records from Plants of Papua New Guinea. 389 records from (Table 2) Distribution of planktonic foraminifera in DSDP Hole core 90-594. 51 records from Planktic foraminifera assemblage in sediment core GIK23066-2. 80846 records from Colección de Lepidópteros del Museo de Zoología 'Alfonso L. Herrera', México (MZFC, UNAM). 211 records from Stadt Königs Wusterhausen. 123677 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 27 records from Hybridization in Umbridae in the Hudson River, New York, with Designation of Neotypes for Umbra limi and Umbra pygmaea.. 101 records from BIRDRACE nabu-rhein-main.de. 53 records from BIRDRACE Taubenhaucher. 331 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_93MC. 33 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, turbidite sequence 3. 138 records from Total foraminifera counts of multinet M11/1_MSN520. 238 records from Abundance of planktic foraminifera at CTD station PS55/081-1. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-23-2. 5 records from Nannofossil abundance of Hole 3-22. 3440 records from Actualización de la base de datos del proyecto H278 Apoidea (Hymenoptera) del Valle de Zapotitlán de las Salinas, Puebla. 1116 records from CUBA:Herbario del Jardín de los Helechos, Centro Oriental de Ecosistemas y Biodiversidad, Santiago de Cuba: BSC-Pteridophyta. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station SEPTEMBER-1995-D4. 3304 records from Planktic foraminifera abundance of Hole 41-369A. 151 records from Planktic foraminifera abundance of Hole 11-104. 180 records from Phytoplankton abundance off Guañape islands in Juli 2003, Peru. 13230 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Conidae. 1445 records from (Table T4) Planktonic foraminiferal stratigraphy of ODP Hole 173-1069A sediments. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 4 records from Pachycondyla nigrita and related species in Southeast Asia.. 1735 records from The Flora of County Clare. 29 records from A new species of Jupiaba Zanata, 1997 (Ostariophysi, Characiformes, Characidae) from the rio Tocantins drainage, Brazil.. 13616 records from Colección de Aves de Colombia del Instituto Alexander von Humboldt. 64 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 958 records from (Table 6) Planktonic foraminifera in ODP Holes 139-856A and 139-857A. 101 records from Nannofossil abundance of Hole 64-476. 2 records from Nannofossil abundance of Hole 74-525A. 3772 records from Fish (KIWE-PI). 54 records from Planktic foraminifera abundance of Hole 15-146. 819 records from (Table T4) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones P7-P8. 1453 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales de afloramiento rocoso del Parque Nacional Natural El Tuparro. 4567 records from Herbarium WRSL, Main Collection. 2913345 records from Especímenes INBio. 46 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction 63-125 µm. 16 records from Assemblage of living benthic foraminifera in sediment core CD145_55818#4, >150 µm. 235 records from Total foraminifera counts from multinet M31/3_MSN905. 76 records from Plasm bearing foraminifera counts of multinet M36/2_MSN1107. 7 records from Sarcodine counts and carbon biomass at station TT008_5-PMOC6. 44 records from (Table F3) Occurrence of some well known benthonic foraminiferal species in samples from DSDP Site 6-49. 69 records from Naturpark Kottenforst-Ville 17.6.09. 1 records from Estudio de los frutos y semillas del género Chenopodium en la Argentina. 1185 records from (Appendix A) Foraminifera and stable carbon and oxygen isotope record of ODP Site 105-646. 5 records from Pollen record of a sediment profile from Lake Teletskoye. 3 records from Analyses of the recent components in the sand fraction of sediment core PS1403-1. 97 records from Range table from planktonic foraminifers in ODP Hole 182-1133B. 44 records from Flora und Fauna in unserer Kita. 43 records from Abundance of epibenthic echinoderms at seafloor photography station PO196_1017. 14882 records from NCSM Mammals Collection. 1373 records from Finnish Entomological Database: Araneae. 68304 records from IICT Herbário LISC. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 9 records from Innenhöfe der Gesamtschule Berger Feld/ Gelsenkirchen. 65 records from Pollen analysis and dinoflagellate cyst of sediment core IOW211670-7. 7774 records from BioGIS - Hamaarag. 279 records from Late Cretaceous and Cainozoic bathyal Ostracoda of DSDP Site 62-463 in the Central Pacific (Fig. 3). 2084 records from (Appendix 1) Census data of planktic foraminiferal faunas together with estimates of mean annual SST for sediment core R657. 90 records from Quaternary radiolarians from offshore eastern New Zealand, ODP Leg 181, Site 1123, relative abundances. 3275 records from Quantitative Phytoplankton data from Irish lakes (EPA). 1 records from Deux especes nouvelles pour la science du genre Eupolybothrus Verhoeff (Lithobiomorpha: Ethopolinae). - Two new species for the science in the genus Eupolybothrus Verhoeff (Lithobiomorpha: Ethopolinae). 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 214 records from Benthos abundance in surface sediment sampled during cruise ANT-V/1. 36 records from Abundance of algae in the Aral Sea. 1851 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Pisces_Types. 290 records from (Table 1) Distribution and numerical abundance of foraminifera of sediment core CRP-3. 2222 records from UWYMV Bird Collection (Arctos). 289 records from Odonata del Museo de Entomología de la Universidad del Valle. 260196 records from DINA. 65 records from (Table 4) Pleistocene nannofossil range chart for ODP Hole 134-827A. 2 records from Ein Beitrag zur Landtierwelt von Korfu. Chilopoda. 1695 records from Field Study Group of the Dutch Mammal Society (NL) - 2005 - Mammal Survey Pol'ana Biosphere reserve, Slovakia. 103 records from Wasserwerkspark (Chemnitz). 58 records from VFD-H. Heidenrod: Mähweide im Wasserschutzgebiet. 69 records from Faunal assemblage of sediment core GS7603-7. 349178 records from AMNH Herpetology Collections. 5 records from Nannofossil abundance of Hole 6-53A. 7 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/091-4. 642 records from Planktic foraminifera counts of sediment core V22-196. 304 records from Planktic foraminifera counts of sediment core V29-173. 372 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 139 records from Revision of the myrmicine ants of the Adelomyrmex genus-group (Hymenoptera: Formicidae).. 8326 records from Derbyshire Biological Records Centre - Derbyshire Invasive Vascular Plants (INNS) 1900 - 2011. 61 records from Wälder im Hainbachtal. 24 records from Counts (2) of calcareous dinocysts along profile Stevns-Klint. 27 records from (Table F3) Occurrence of some well known benthonic foraminiferal species in samples from DSDP Site 6-50. 2118 records from Flora de macroalgas del litoral oaxaqueño. 17369 records from MfN - Auchenorrhyncha Collection. 346511 records from ARGOS Satellite Tracking of animals. 29876 records from European Moth Nights. 1371 records from Planktic foraminifera assemblage in sediment core GIK16773-1. 6782 records from Zooplankton Abundance Based on Taxa and Life Stages or Size. 316 records from Moss species from Heard Island, 1987 and 2000. 536 records from Walldorf-Wiesloch: "Natur über den Gleisen". 621 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 234 records from Occurrence of mammalia relicts at site Pestera Cioarei. 324 records from Phytoplankton abundance in surface water in September 1997, Chimbote, Peru. 2651 records from KTU Pteridophyta. 2193 records from Hemiptera (Homoptera) collection of National Museum of Nature and Science. 422 records from (Table T1) Planktonic and benthic foraminifer abundance of ODP Hole 183-1138A. 86774 records from Queen Victoria Museum Art Gallery provider for OZCAM. 49 records from New species of the amphiliid catfish genera Amphilius, Doumea and Phractura and the taxonomy of Paramphilius from West Central Africa (Siluriformes, Amphiliidae).. 71 records from RSPB - Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010.. 88 records from Microfossil abundance of Hole 16-157. 290 records from Planktic foraminifera counts of sediment core RC11-134. 83 records from Admiralty Bay Benthos Diversity Data Base (ABBED). Cumacea.. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 5 records from Occurrence of mammalia relicts at site Victoria Cave. 7 records from (List 1) Fossil record of Mollusca in Schleswig-Holstein, Germany. 43298 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 133 records from Total foraminifera counts of multinet PO247/2_MSN1379. 137 records from Planktic foraminifera counts of sediment core V28-25. 630 records from (Figure 3) Distribution chart of benthic foraminifers in ODP Site 126-790. 613 records from Distribution of dinoflagellate cycst at ODP Site 123-765 (Table 1). 1427 records from Evaluación del riesgo de extinción de setenta y tres especies de lagartijas (Sauria) incluidas en la Norma Oficial Mexicana-059-SEMARNAT-2001. 9558 records from Modern planktic foraminifera assemblage from surface sediment samples used as reference data set for the reconstruction of Atlantic sea surface temperatures during the last glacial maximum (LGM). 463 records from Range table from planktonic foraminifers in ODP Hole 171-1052E. 3096 records from Biological Records Centre - Mosquito Recording Scheme. 5 records from (Table 1) Late Maastrichtian calcareous nannofossils in DSDP Hole 22-212. 22854 records from National Botanic Garden Belgium - Myxomycetes. 118 records from A Tenebrionid beetle’s dataset (Coleoptera, Tenebrionidae) from Peninsula Valdés (Chubut, Argentina). 676 records from (Table 4) Distribution of planktonic foraminifera in middle Miocene sediments of DSDP Hole 94-608 in the North Atlantic. 48 records from Planktic foraminifera abundance of Hole 25-241. 197 records from (Table 7) Relative abundance of benthic foraminifera in ODP Hole 112-683A. 1794 records from Elephant Seal Sightings, Heard Island. 156948 records from NBI. 176 records from INSECT COLLECTION. 12 records from Microplankton abundance at bottle station SEPT-1999-K9. 79 records from Occurrence of mammalia relicts at site Rislisberghöhle. 83 records from Planktic foraminifera abundance of Hole 40-361. 85 records from Range table from benthic foraminifers in ODP Hole 154-929B. 1257 records from Faun. 2498 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1168A sediments. 1 records from Nothrus convexus. 40 records from Öhmdwiesen und Göldern (Konstanz). 174 records from Colecciones Zoológicas de la Universidad de León, Colección de Gasterópodos. 596 records from Lower Albian l`Arboudeysse section (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France. 174 records from Total foraminifera counts from multinet M31/3_MSN915. 38998 records from Countryside Council for Wales - 1996 - 2005 CCW Marine Intertidal Phase 1 species dataset. 52 records from Total foraminifera counts of multinet M21/4_MSN713. 45 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1385. 34 records from Foraminifera species abundances from tow TT007_9-MOC18. 215 records from (Table 2) Distribution of sinsitral and dextral fohsellids in middle Miocene sediments of ODP Hole 130-806B from the Ontong Java Plateau, Pacific Ocean. 9 records from Microzooplankton abundance and biomass at station TT043_6-1. 4 records from Microzooplankton abundance and biomass at station TT054_17-21. 1698 records from MNA Italica 2004_Rauschert dredge_Ross_sea_Mollusca_lgp. 2 records from Nannofossil abundance of Hole 58-442B. 823 records from Planktic foraminifera counts of sediment core V17-165. 13 records from (Table 2f) Nannofossil distribution chart of petroleum well Montara-2. 3318 records from ZOOLOGIA_FCNO_UDEC_CL Foraminiferos_01 (OBIS South America, SOUTH PACIFIC NODE). 1296 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC13-229. 37 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100800. 23 records from Planktic foraminifera abundance of Hole 29-284A. 2 records from Benthic foraminifera abundance of Hole 42-376. 16 records from Qualtitative analysis of calcareous dinocysts along profile Stevns-Klint. 1425 records from (Fig. 12) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 50-416A in the North Atlantic. 40 records from The identity of Pseudecheneis sulcata (M'Clelland, 1842), with descriptions of two new species of rheophilic catfish (Teleostei: Sisoridae) from Nepal and China.. 2 records from Ueber Chilopoden aus westbalkanischen Hoehlen. 28383 records from Notes from the Mycology Herbarium, Oslo (O). 56302 records from Kathryn Kalmbach Herbarium. 121 records from (Table 2) Relative contents of planktonic foraminifera in bottom sediments from the Ashadze-1 Hydrothermal Field. 66 records from Schulhof A.-Lindgren-Schule (Elmshorn). 134 records from (Table 1) Benthic foraminiferal distribution at ODP Site 127-794. 5817 records from SMNS Palaeontological collection - Amber. 6 records from Nannofossil abundance of Hole 7-63. 12 records from Nannofossil abundance of Hole 74-528A. 44 records from (Table 6) Distribution of nannofossils in DSDP Hole 87-583G. 1 records from Nothrus bicarinatus. 2 records from Neue Milbenarten aus Kärnten. 12 records from Spider hosts (Arachnida, Araneae) and wasp parasitoids (Insecta, Hymenoptera, Ichneumonidae, Ephialtini) matched using DNA barcodes. 106920 records from Naturalis Biodiversity Center (NL) - Lepidoptera. 380 records from (Table 4) Benthic foraminiferal genera in DSDP Core 95-612-16 and 95-612-17. 1 records from Nothrus palliatus. 1275 records from (Table T6) Planktonic foraminifera stratigraphy of ODP Hole 198-1209, Zones P12-P18. 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 70 records from Birdrace-WdW-Wilder_Westen-Viersen. 15 records from Urwald 2 (Bad Waldsee). 54 records from Biotope im Schulumfeld. 119 records from Assemblage of living benthic foraminifera in sediment core GeoB4915-3. 162 records from Assemblage of living benthic foraminifera in sediment core GeoB4916-4. 227 records from Total foraminifera counts from multinet M31/3_MSN916. 26 records from Phytoplankton abundance in surface water in 1997, Ancon, Peru. 668 records from Phytoplankton abundance during OCEANIA cruise Oceania90. 5 records from The nematoda fauna of sediment samples of Sarso Islands, Red Sea (Table 5). 18 records from Smear slide analysis on sediment core GeoB4206-1. 101 records from Relative abundance of coccosphere-units of sediment core GIK23411-5. 56 records from Nanoplankton abundance at station GeoB2021-3. 4 records from Nannofossil abundance of Hole 9-81. 4 records from Nannofossil abundance of Hole 77-540. 10898 records from Himenópteros Parasíticos en México (UANL). 227 records from (Table 6) Chemical composition of basalts from the Mid-Atlantic Ridge in the Doldrums Fault Zone. 127 records from Birdrace_Schräge_Vögel-Herford. 71 records from Birdrace-NAJU_Aspach-Rems/Murr. 3378 records from (Appendix 1) Census data of planktic foraminiferal faunas together with estimates of mean annual SST for DSDP Site 90-594. 1 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/565-1. 15 records from Description of lithologic section units of IODP Hole 325-M0032A. 329 records from Fig. 11: Benthic foraminifera assemblage of sediment core MD97-2131. 1654 records from (Appendix A5) Relative abundances of planktonic foraminifera of sediment core GeoB1711-4. 582 records from (Table 2) Relative abundance of planktic foraminifera in Maastrichtian sediments of DSDP Hole 3-21 from the Rio Grande Rise, South Atlantic Ocean. 218 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 248 records from Range table from benthic foraminifers in ODP Hole 198-1210A. 5 records from Two new species of Exallonyx Kieffer (Hymenoptera: Proctotrupidae) from China, with a key to Chinese species.. 240 records from Phytoplankton abundance in surface water in July-August 1996, Pisco, Peru. 226 records from Molecular and morphological characterisation of new species in the trapdoor spider genus Aname (Araneae: Mygalomorphae: Nemesiidae) from the Pilbara bioregion of Western Australia. 213 records from Poliquetos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMUV). 10175 records from Seil Natural History Group - SNHG Biological Records Dataset. 335 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1170D sediments. 21663 records from Monitoring data from the federal state Saxony-Anhalt (Germany). 2464 records from (Table 2) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-698A. 503 records from Biodiversidad acuática del río Amacuzac, Morelos, México. Invertebrados. 1536 records from (Table 5) Distribution of planktonic foraminifera in the latest Pliocene to Holocene section of ODP Hole 149-898A. 1431 records from (Table 10) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-712A. 11903 records from The Myxomycetes Collection at the V. L. Komarov Botanical Institute, St. Petersburg. 166 records from Außenfeuerstelle Königsbol (Hartheim/Meßstetten). 20 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station MARCH-1995-D2. 226 records from Range table from planktonic foraminifers in ODP Hole 180-1109D. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Fregatidae. 19 records from Scottish Wildlife Trust - Small Cow-wheat distributions for Scotland 1999 to 2005. 94 records from (Appendix 4) Calcareous nannofossils in ODP Hole 113-689B. 102 records from (Figure 3) Selected benthic foraminifera measurements from sediment core AvH248260-1, Ameralik Fjord, SW Greenland. 184156 records from The Flora of County Waterford. 17 records from MVZ Herp Observations (Arctos). 434 records from (Table 4) Benthic foraminiferal community at DSDP Hole 94-609B. 88412 records from PACA-AGP - Herbarium Anchieta. 1 records from Celaeno obsoleta. 17824 records from SJRP - Herbário de São José do Rio Preto. 1473 records from (Appendix 2, Part 1) Distribution of Eocene to Recent benthic foraminifera in ODP Site 113-689. 178 records from (Table SD1, Fig. 2) Benthic foraminiferal abundances, preservation states and thickness to diameter ratios from IODP Hole 310-M0005D. 6 records from Sediment properties of core PLG93_BCORE1. 525 records from Range table from planktonic foraminifers in ODP Hole 155-941A. 763 records from Bisons Collection. 311 records from Avena wild species VIR Herbarium. 3219 records from (Figure 6) Planktonic foraminifera distribution in ODP Hole 130-803D. 33 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Ramphastidae. 261 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 52381 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 7551636 records from BirdLife Australia, Birdata. 18 records from Plasm bearing foraminifera counts from multinet M31/2_MSN889. 102 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 104 records from Plasm bearing foraminifera counts of multinet M21/2_MSN649. 1726 records from KTU Pinophyta. 250 records from (Appendix) Relative abundance of some calcareous nannofossils in ODP Hole 119-738C. 288 records from Gorgonacea specimens of Kuroshio Biological Research Foundation. 40 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 6 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR50. 308 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 1087 records from SMNS Palaeontological collection - Tertiary and quaternary invertebrates. 169 records from Expedition "Schulgelände". 114 records from BIRDRACE VIE will rock you!. 233 records from Distribution of planktic foraminifera (125-250 µm) of sediment core GIK23059-3. 12 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5110-4. 378 records from Size of planktic foraminifera at CTD station PS55/077-1. 1683 records from (Appendix 2) Distribution of planktonic foraminifera in the last 70 kyr of sediment core MD95-2043 from the western Mediterranean Sea. 38 records from Phytoplankton abundance at bottle station A1/52. 121 records from (Table 1) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-541. 510 records from Planktic foraminifera counts of sediment core V20-242. 777 records from (Table 2) Distribution of benthic foraminifera in ODP Hole 120-748A. 3422 records from Distribución y aspectos taxonómicos de los corales pétreos (Anthozoa: Scleractinia) del Pacífico mexicano. 16 records from Description of lithologic section units of IODP Hole 325-M0057A. 1167 records from Macroinvertebrate Data BOKU. 90 records from Late Albian Col de Palluel (SE France, Niveau Breistroffer): results from planktic foraminifera. 268160 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 35 records from Range table from planktonic foraminifers in ODP Hole 139-858D. 16324 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 26 records from Living benthic foraminifera at station M33/1_MC-25 (EAST), size fraczion 63-125 µm. 773 records from Distribution of calcareous foraminifers in sediment core Well 6406/11-1. 26 records from Assemblage of living benthic foraminifera in sediment core CD146_55901#11, >150 µm. 112 records from Total foraminifera counts of multinet M33/1_MSN1029. 198 records from Total foraminifera counts from M35/1_MSN1047. 159 records from Total foraminifera counts of multinet M21/6_MSN789. 244 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 9 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 15 records from Benthic macrofauna abundance of sediment core 13078-013. 936 records from Bats of Poland. 17 records from (Table 2h) Nannofossil distribution chart of petroleum well Swan-3St. 3702 records from Vertebrados terrestres del parque nacional Cañón del Sumidero, Chiapas, México. 9 records from (Table 4) Abundance of microalgae in sinking sedimentary material from sediment traps in the northeast Black Sea in September-October 1999. 1789 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V22-174. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station OCTOBER-1994-D4. 1 records from Occurrence of mammalia relicts at site Ejstrup. 56 records from Microzooplankton abundance measured on water bottle samples at station PS65/470-1. 15 records from Abundance and composition of meiobenthos in surface sediments at Fladen Ground stations in August 1975, North Sea (Table 4). 8 records from Nannofossil abundance of Hole 60-458. 572 records from Planktic foraminifera counts of sediment core V04-32. 20114 records from Molluscus specimens of Toyohashi Museum of Natural History. 31 records from Occurrence of mammalia relicts at site Sainte-Eulalie. 93 records from Range table from planktonic foraminifers in ODP Hole 180-1111A. 6 records from (Table 1) Dinoflagellate cyst zonations at ODP Site 202-1233. 41 records from Nine genera of Eucnemidae (Coleoptera) new to Peru, with a key to Peruvian genera. 31 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto39-47. 180 records from Paul-Gerhardt-Schule Dassel. 30 records from Assemblage of living benthic foraminifera in sediment core CD145_55830#3, 63-150 µm. 133 records from Abundance of planktic foraminifera at CTD station PS55/018. 4 records from Stable carbon and oxygen isotope record of Cretaceous planktonic foraminifera from DSDP (Table 1). 5 records from Distribution of Quinqueloculina sp. in sediment core 13200-020. 201 records from Mycological collections of the University of Tartu. 2631 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-HEPATICAE. 92 records from Nottekanal, Klasse 7 - 10. 17966 records from Ornithology Collection. 73 records from Fossil (JNHM-FO). 7000 records from CCBER Ornithology Collection. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 94 records from (Table 1) Some abiotic factors and distribution of benthic foraminifers in surface layer of bottom sediments from the littoral zone of the Kunashir Island (Sea of Okhotsk side). 61234 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1999) (AfrOBIS). 497 records from Relative abundance of Quaternary foraminifera of sediment core CRP-1 (App. 1). 288 records from Planktic foraminifera abundance of Hole 94-610A. 960 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 5 records from Range table from benthic foraminifers in ODP Hole 181-1120C. 56 records from Range table from benthic foraminifers in ODP Hole 181-1121B. 2324 records from Distribution of living benthic foraminifera in surface sediments of the Norwegian Sea (Table 2). 140 records from Bunger Hills, 1999/2000 survey - nest sites of snow petrels Pagodroma nivea. 11591 records from (Table T6) Foraminifer distribution in ODP Hole 188-1167A sediments. 1 records from Hoplophora carinata. 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 7 records from A new species of Trichomycterus (Siluriformes: Trichomycteridae) from south Brazil and redescription of T. iheringi (Eigenmann).. 4 records from Microzooplankton abundance and biomass at station TT054_26-21. 150 records from Redescription and generic placement of the spider Cryptachaea gigantipes (Keyserling, 1890) (Araneae: Theridiidae) and notes on related synanthropic species in Australasia. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-28-3. 7414 records from HJ - Herbario Jataiense Prof. Germano Guarim Neto. 12 records from Chenopodieae. 14830 records from Parasitic Platyhelminthes Collections. 1355 records from Planktic foraminifera abundance of Hole 18-173. 39 records from Planktic foraminifera abundance of Hole 28-265. 319 records from Dinoflagellate abundance of Hole 38-338. 123006 records from Finnish Entomological Database: Diptera. 129 records from Nannofossil abundance of Hole 29-284. 1963 records from Range table from planktonic foraminifers in ODP Hole 157-953C. 345 records from Range table from nannofossils in ODP Hole 199-1218A. 76 records from Live (Rose Bengal stained) benthic foraminifera from surface sediments of the Indian and Pakistan continental margin (Table 1). 406 records from (Table 4) Distribution of foraminifera in the Miocene section of ODP Hole 133-816C. 30409 records from Birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 872 records from Colección de Entomología - Hymenoptera - Parasitica. 3 records from New synonym of Tipula (Vestiplex) wahlgrenana Alexander, 1968 (Diptera: Tipulidae). 17520 records from Arthropod collection, Tromsø Museum. 2265 records from Algae, Specimens, Agder naturmuseum (KMN). 8220347 records from OEH Atlas of NSW Wildlife. 968 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones Palpha-P3b. 106 records from NSG Forst Zinna-Jüterbog-Keilberg. 394 records from Distribution of agglutinated foraminifers in sediment core Well 6406/11-1. 671 records from (Appendix B) Benthic foraminiferal abundances and principal component scores in middle to late Pliocene sediments of DSDP Hole 94-610A from the North Atlantic. 46 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/427-6. 10 records from Phytoplankton abundance at station Sechin_2003-12-17_2, Casma, Peru. 39 records from Megafauna abundance and biomass from trawl samples obtained during cruise DI231. 15918 records from BANDASCA, BAse de DAtos sobre SCArabaeidae. 128 records from (Table 5) Distribution of the large, many-chambered Globigerinelloides species in the Calabianca section. 17876 records from Mycology Herbarium, Trondheim (TRH). 138 records from Relative abundance of live benthic foraminifera of sediment core M5/2_107MC. 751 records from (Table T5) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1212B, Shatsky Rise, Pacific Ocean. 37 records from A brief review of Triplophysa (Cypriniformes: Balitoridae) species from the Tarim Basin in Xinjiang, China, with description of a new species.. 1069 records from ZFMK Sound Archive. 58031 records from Colección nacional de zoología. 10061 records from Collembola collection of Arne Fjellberg, Norway. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 3175 records from Centre for Genetic Resources, the Netherlands, Indigenous Trees and Shrubs. 231131 records from MVZ Mammal Collection (Arctos). 1 records from On the Chilopoda from Turkey. 101 records from Birdrace-Herford-Birder-Herford. 160 records from Waldstück Bremerhagen LK Bio Kl. 12. 126 records from BIRDRACE Die Schwenker-Birder. 75 records from BIRDRACE Die Kartoffelsäcke. 161 records from Total foraminifera counts of multinet M21/3_MSN671. 97 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1383. 21 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD59. 482 records from Kühmark bei Wetzlar. 39 records from Ostracoda abundance of Hole 24-238. 4 records from Nannofossil abundance of Hole 5-32. 6 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 15663 records from Collection Herpetologie - SNSD. 3381 records from (Table 10B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-588A. 66 records from Langes Tannen(LMS), Klasse 5d. 49 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC468. 3 records from Nannofossil abundance of Hole 20-199. 12 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-1. 978 records from Aves de las reservas de la biosfera de Durango: La Michilía y Mapimí. 83 records from Frau Voss. 66 records from Range table from planktonic foraminifers in ODP Hole 151-909A. 871 records from Benthic foraminiferal assemblages (dead), surface data. 6887 records from (Figure 13) Distribution of middle Miocene through middle Pleistocene planktonic foraminifera in ODP Hole 132-810C. 1988 records from (Appendix 2) Benthic foraminifera in ODP Hole 160-963A. 2322 records from (Table AT8) Planktonic foraminiferal stratigraphy of ODP Hole 182-1134A. 5 records from A new cleaner goby of the genus Elacatinus (Teleostei: Gobiidae), from Trindade Island, off Brazil.. 1 records from Murcia ephippiata. 105 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1372. 3 records from Nannofossil abundance of Hole 9-80. 109 records from Broadland Environmental Services Limited - Reptile distribution along the River Bure, Broadland (2010). 2698297 records from Eremaea. 1420 records from Planktic foraminifera abundance of Hole 49-407. 14 records from Two new glyptosternine catfishes (Teleostei: Sisoridae) from Vietnam and China.. 635 records from Distribución, estructura poblacional y variación genética de algunas especies de pinos en peligro de extinción en México. 318 records from Field Study Group of the Dutch Mammal Society (NL) - 2006 - Mammal Survey Galicica National Park, Macedonia. 1309 records from Benthic foraminifera distribution of sediment core BP01-62/06. 13746 records from CNIN/Coleoptera. 2 records from Range table from planktonic foraminifers in ODP Hole 139-855D. 255 records from Range table from planktonic foraminifers in ODP Hole 170-1039B. 182 records from Range table from benthic foraminifers in ODP Hole 182-1128B. 29367 records from Geographic distribution of dinoflagellate cysts in surface sediments. 67 records from Inventario Murciélagos Finca Naranjito, Aracal, Yopal, Casanare. 3509 records from Entocytheridae (Ostracoda) World Database. 433 records from (Table S1) Palynology of IODP Hole 302-M0004A. 9 records from Countryside Council for Wales - Sightings & Miscellaneous Data from Countryside Council for Wales (CCW), 2008 onwards. 233 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 9792 records from International Collection of Microorganisms from Plants - New Zealand National Microbial Collection. 194 records from Landschaftsschutzgebiet Eulenkopf (VG Otterbach). 140 records from (Table 2b) Downcore distribution of live benthic foraminifera of sediment core PS1394-3, Weddell Sea. 324 records from Total foraminifera counts from multinet M32/5_MSN974. 51 records from Plasm bearing foraminifera counts from multinet SO119_MSN1285. 199 records from Palynomorpha in sediment core PM9462-4 from the Laptev Sea. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-4. 23315 records from Gwaii Haanas Invertebrates (OBIS Canada). 102 records from Streuobstwiese RSG (Cham). 4 records from Oribatids from Switzerland IX (Acari: Oribatidae, Mycobatidae 2) (Acarologica Genavensia CI). 331 records from Range table from planktonic foraminifers in ODP Hole 141-859A. 5583 records from All observations extracted from the Flora of Northumberland and Durham 1831. 734 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Icteridae. 85 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Recurvirostridae. 44770 records from Borror Lab of Bioacoustics (BLB), Ohio State University. 149 records from (Appendix A) Palynofacies raw counts of DSDP Hole 38-338. 274 records from Bernhardsthal. 39 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction 30-63 µm. 161 records from Total foraminifera counts from multinet SO119_MSN1286. 66 records from Plasm bearing foraminifera counts of multinet M21/2_MSN642. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_2-CTD26. 8 records from Mean values of fractionated primary production and protozoan abundance from the photic layer collected at 50 m depth in Mejillones Bay. 15 records from Abundance of Elminius modestus in 2007-03 from an experiment in the Wadden Sea off List, Sylt. 5 records from Abundance of radiolaria at station LV28-66-1. 81 records from (Table 10) Occurrence of benthic foraminifera in ODP Hole 112-688E, Part I. 822 records from Isotope tracer experiment: nematode abundance. 2670 records from Colección Teriológica y Ornitológica de la Universidad Tecnológica del Chocó. 59799 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 777 records from INRA-Versailles Arabidopsis natural variants. 1 records from On the Chilopoda from Turkey. 165 records from Total foraminifera counts from multinet M31/3_MSN903. 62 records from Plasm bearing foraminifera counts of multinet M21/5_MSN728. 1054 records from Naturhistorisches Museum Mainz, Herbarium Oesau. 421 records from Planktic foraminifera counts of sediment core RC09-162. 18 records from Crustacea in surface sediments off Sylt collected during Heincke cruise HE218. 544 records from (Table 1) Stratigraphic distribution of new marine palynomorph species recorded for the Miocene and lowermost Pliocene of ODP Hole 105-646B. 686 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Friedrich Heincke cruise FHE238. 171 records from Foraminifera abundance of sediment core C1960.201. 626 records from (Table 2) Benthic foraminifera distribution in sediment core ASV11-880-3. 180 records from Entdeckertour am Muldestausee. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station APRIL-1995-D4. 2827 records from (Figure 5) Distribution of benthic foraminifers in the upper Eocene, Oligocene, and Quaternary of DSDP Hole 71-511. 1 records from Dinoflagellates, pollen and spore abundance of Hole 29-281. 420 records from Reptilia Collection of Museum and Institute of Zoology PAS. 288 records from Size of planktic foraminifera at CTD station M39/4_402CTD-55. 12717 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 37 records from Plasm bearing foraminifera counts of multinet M27/2_MSN879. 41884 records from Museu Paraense Emilio Goeldi - Ornithology Collection. 46 records from Nannofossil abundance of Hole 26-254. 9 records from Nannofossil abundance of Hole 26-255. 15 records from Benthic macrofauna abundance of sediment core 13077-093. 1597 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Historico_cofc). Facultad de Ciencias. Universidad de Córdoba. 152 records from Sonnentaugemeinschaft. 30 records from Occurrence of mammalia relicts at site Stematia. 6 records from Planktic foraminifera abundance of Hole 4-24. 94 records from (Table 2) Occurrence of the most abundant nannofossil taxa in middle Cretaceous sediments of ODP Leg 129 sites. 1076 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Tuluá, Valle del Cauca. 26 records from Kinderbauernhof Pinke Panke - Berlin Pankow. 117 records from Naturschutzgebiet Kochertgraben. 95 records from BIRDRACE BiBi. 11 records from Microzooplankton abundance and biomass at station TT045_2-1. 69 records from Relative abundance of coccolith species in surface sediment samples from the Mid-Atlantic Ridge. 47 records from Physical properties, geochemistry and ostracoda abundance of sediment core Lz1080. 1620 records from (Figure 5) Distribution of planktonic foraminifers in the Cenozoic sediments of DSDP Hole 71-513. 4 records from Range table from planktonic foraminifers in ODP Hole 141-862C. 2 records from Benthic foraminifera abundance of Hole 42-374. 56685 records from MISS_DC_01MAR2006. 1 records from The ant genus Pseudaphomomyrmex Wheeler, 1920 a junior synonym of Tapinoma Foerster, 1850.. 6 records from Microzooplankton abundance and biomass at station NBP97-08-08-1. 27 records from Smear slide analysis on sediment core GeoB4212-2. 6 records from A new genus and five new species of Astieae (Araneae: Salticidae) from Australia, with remarks on distribution. 48 records from Artenerfassung für Jedermann in der Grundschule Kirchboitzen. 14 records from Occurrence of recent nannoplankton in multi-net sample at M1_NET243, Arabian Sea (Fig. 2). 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-019. 12 records from Benthic macrofauna abundance of sediment core 13200-020. 599 records from Planktic foraminifera counts of sediment core V26-41. 141 records from (Table 2) Relative abundance of benthic foraminifera in ODP Hole 112-680B. 324 records from (Appendix B) Planktic foraminiferal assemblages from ODP Holes 113-689B and 113-690B. 3 records from Analyses of the recent components of sediment core PS1401-2. 35 records from Range table from benthic foraminifers in ODP Hole 181-1124C. 31 records from Description of a new species of Acestridium (Siluriformes: Loricariidae) from Colombia.. 3772 records from BOS Arthropod Collection of University of Oviedo (Spain): Opiliones. 133 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Parulidae. 3329 records from The Pisces Collection at the Staatssammlung für Anthropologie und Paläoanatomie München. 25 records from Glyptothorax botius (Hamilton, 1822), a valid species of catfish (Teleostei: Sisoridae) from northeast India, with notes on the identity of G. telchitta (Hamilton, 1822).. 544 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 11700 records from (Figure 4) Distribution of benthic foraminifers in the Upper Cretaceous of DSDP Hole 71-511. 364 records from Nekton and plankton counts from neuston net (300 µm) hauls of cruise GAE 1975/76. 50939 records from Instituto Pirenaico de Ecología-CSIC: Herbarium JACA. 17979 records from Herbario EMMA. Herbario de la Escuela Técnica Superior de Ingenieros de Montes. UPM. 900 records from Percentages of planktonic foraminifera species in sediment core V30-36. 45 records from Pfrimmersbachtal. 20 records from Occurrence of mammalia relicts at site Niederlehme. 39 records from Range table from planktonic foraminifers in ODP Hole 139-856B. 30 records from Range table from planktonic foraminifers in ODP Hole 152-916A. 78 records from Range table from planktonic foraminifers in ODP Hole 167-1019C. 255439 records from R. L. McGregor Herbarium Vascular Plants Collection. 1 records from Carabodes coriaceus. 3341 records from SORO - Herbário do Centro de Ciências e Tecnologias para a Sustentabilidade. 458 records from Barley French National Collection. 601 records from Dinoflagellate cyst species of sediment core GeoB10732-3. 86 records from Naturerlebnisraum Koppelsberg (Plön). 77 records from Plasm bearing foraminifera counts from multinet SO119_MSN1303. 783 records from Phytoplankton abundance in surface water during cruise CD61. 128 records from Phytoplankton abundance at station CD47_2805C#5. 34 records from Phytoplankton abundance and species composition in the North Balearic Sea in April 2003. 46 records from Aktion Wiese und Wegrain Gitzenheide. 47 records from Nannofossil abundance of Hole 86-577. 5 records from Nannofossil abundance of Hole 67-499B. 666 records from (Table 2) Species composition of agglutinated foraminifers from the abyssal zone of the Pacific Ocean. 78 records from (Table T1) Abundance of dinoflagellate cysts and other palynomorphs in ODP Hole 184-1148A. 60163 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 50 records from Artensuche auf den Elbwiesen in Radebeul. 1433 records from (Appendix Table 1) Relative abundances of calcareous nannofossil in the total assemblage of ODP Hole 177-1090D. 1553 records from Colección preservada Jardín Botánico de la Patagonia Extraandina. 6 records from Microzooplankton abundance and biomass at station NBP97-03-09-1. 18 records from Phytoplankton abundance at bottle station GOM3/1. 88 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2214-1. 42 records from Stadtwald Heide. 50 records from NABU-Fläche am Bösselhausener Weg. 51 records from Coccoliths in sediment core PS1295-4. 225 records from Nannofossil abundance of Hole 15-154A. 5 records from Diatom abundance measured on water bottle samples at station PS58/043-2. 81105 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1998) (AfrOBIS). 1796 records from Sea shell specimens database of Mr. Toru Ueda collection, Shizuoka Prefecture Museum of Natural History. 7014 records from (Figure 6) Distribution of planktic foraminifera of ODP Hole 159-958A. 186 records from Schulhof Goethe-Gymnasium (Emmendingen). 617 records from Planktic foraminifera abundance of Hole 23-223. 3 records from Planktic foraminifera abundance of Hole 54-424B. 109 records from Planktic foraminifera abundance of Hole 37-333A. 145 records from Planktic foraminifera abundance of Hole 73-524. 85 records from Range table from planktonic foraminifers in ODP Hole 151-909C. 240 records from Range table from benthic foraminifers in ODP Hole 175-1075A. 672 records from Colección de Entomología - Curculionidae. 25 records from Assemblage of living benthic foraminifera in sediment core SO117_MC469, 63-125 µm fraction. 9494 records from Colección de plantas vasculares del Herbario "Jaime Andrés Rodríguez". LEB. 42 records from (Appendix 7) Abundance of Neogloboquadrina pachyderma in sediment core MD01-2444. 326 records from Elasmobranquios del sistema laguna Chantuto-Panzacola y Carretas-Pereyra de la Reserva de la Biósfera La Encrucijada, Chiapas. 2618 records from MAR-ECO (EurOBIS). 49009 records from MBML-Herbario - Herbário Mello Leitão. 463 records from Facultad de Ciencias Exactas y Naturales Universidad de Buenos Aires Coleccion BAFC de Hongos. 1423 records from Raw counts of dinoflagellate cysts of sediment core DP30PC. 5612 records from Marine Biological Association - 2005-Ongoing United Kingdom MarLIN Shore Thing timed search results. 10 records from Feuchtwiesen Wippertal bei Wippra. 30 records from Phytoplankton abundance in surface water in 2001, Ancon, Peru. 2 records from Nannofossil abundance of Hole 1-1. 2 records from Nannofossil abundance of Hole 10-87. 4 records from Distribution of Quinqueloculina sp. in sediment core 13200-045. 19885 records from Natural History Museum Rotterdam (NL) - Chordata collection. 48 records from Abundance of phytoplankton in surface water during THALASSA campaign PROSOPE. 26753 records from Fish collection of the Museum of Nature and Human Activities, Hyogo. 21593 records from CNCR/Colección Nacional de Crustaceos. 1083 records from Percentages of planktonic foraminifera species in sediment core V29-144. 133 records from Naturschutzgebiete um das Christliche-Spalatin-Gymnasium Altenburg. 40 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200500. 1974 records from Range table from planktonic foraminifers in ODP Hole 160-967E. 42507 records from Bird Collection of Museum and Institute of Zoology PAS. 3 records from Nannofossil abundance of Hole 1-7. 39835 records from Jardín Botánico de Córdoba: Herbarium COA. 5644 records from (Appendix 1) Planktonic foraminifera abundances in ODP Site 181-1123. 3 records from Nannofossil abundance of Hole 22-212. 13 records from Nannofossil abundance of Hole 94-607A. 414 records from (Table A a) Relative contributions of planktic foraminiferal species in sediment trap series L1/K276-22 at 2000 m water depth. 234 records from (Table 2) Selected planktonic foraminiferal species and other microfossil data for sedimentcore P69. 950 records from (Appendix 2) Late Cretaceous benthic foraminifera of ODP Site 207-1259. 580 records from Herpetofauna de la reserva de la biósfera Valle de Tehuacán-Cuicatlán (etapa final). 1394 records from Avifauna de la Isla de Cozumel, Quintana Roo_1. 27 records from (Table 1) Fauna composition of the community of Amphiodia urtica - Nephtys ferruginea in bottom sediments from the central part of the shelf in the California upwelling zone. 899 records from Collection Insecta fossil - SMF. 150169 records from UWFC Ichthyology Collection. 7 records from (Table 4) Concentrations of PCBs and MeSO2-PCBs in adipose tissue of polar bears (Ursus maritimus) between 1991-2007. 97 records from CNIN/Tipos Hymenoptera. 44 records from Leegmoor (Moormerland/Leer). 689 records from Range table from planktonic foraminifers in ODP Hole 152-919B. 1101 records from Colección de Entomología - Orthoptera. 85 records from Birdrace-Die_Paradiesvögel-Herford. 21 records from LBV-Kindergruppen Markt Tussenhausen. 192 records from (Table AT1) Grain size distribution and stable isotope record of benthic foraminifera of ODP Hole 175-1085A. 2810 records from REVIZEE Score Sul / Bentos (OBIS South America, BRAZIL). 125 records from Artenbestimmung. 33 records from Range table from planktonic foraminifers in ODP Hole 175-1078B. 41 records from Range table from planktonic foraminifers in ODP Hole 180-1110B. 10 records from Abundance of epibenthic echinoderms at seafloor photography station PO196_996. 662 records from RSPB - Snipe survey of key sites in Britain in 2006 (RSPB and Natural England). 4 records from Two new species of the genus Chlopsis (Teleostei: Anguilliformes: Chlopsidae) from the Southwestern Pacific.. 18 records from Two new fish species of the genus Puntius Hamilton (Cyprinidae) from Manipur, India, with notes on P. ticto (Hamilton) and P. stoliczkanus (Day).. 424 records from Field Study Group of the Dutch Mammal Society (NL) - 2011 - Mammal Survey Biokovo Nature Park, Croatia. 2413 records from Literature based species occurrence data of birds of North-East India. 113 records from Tornoer Teich. 147 records from Total foraminifera counts of multinet M10/2_MSN295. 11 records from Microzooplankton abundance and biomass at station TT043_28-1. 229 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS1756-5. 16 records from (Table 3) Contusotruncana contusa morphotypes in DSDP Hole 74-527. 2288 records from (Table 2) Distribution of microfossils in the Barrow Group of ODP Site 122-763. 815 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Belgica cruise BG86/1. 11459 records from Herbario de la Universidad de Sevilla, SEV-Historico. 1221 records from NBM Unionoids. 9319 records from Itami City Museum of Insects. 2115 records from Planktic foraminifera assemblage of sediment core ELT49.021-PC. 150 records from Vegetatively propagated Allium collection. 56 records from Draposa, a new wolf spider genus from South and Southeast Asia (Araneae: Lycosidae). 4943 records from Collembola Collection. 52 records from A new species of Cordyligaster Macquart, reared from caterpillars in Area de Conservacion Guanacaste, northwestern Costa Rica. 15474 records from Herbarium Erlangense. 18 records from Thirteen new records of ferns from Brazil. 378 records from (Figure 10) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-537. 1 records from (Table 4) Thecosomata in ODP Hole 134-831A. 51900 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 479 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 90 records from VFD-RP: Taunus: Kirchenweide Köpplers. 40 records from Plasm bearing foraminifera counts of multinet M21/5_MSN733. 8 records from Microzooplankton abundance and biomass at station NBP97-03-16-1. 284 records from Botanical collection of the National Museum. 7 records from Nannofossil abundance of Hole 9-78. 42 records from Ostracoda abundance of Hole 48-406. 260 records from Range table from ostracoda in ODP Hole 144-873B. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/545-1. 13 records from Benthic macrofauna abundance of sediment core 12930-073. 1603 records from Fossil (MNHM-FO). 2072 records from Estación Experimental de Zonas Áridas (CSIC) EEZA - Aves. 14590 records from Colección de Mamíferos de la Sierra Volcánica Transversal de México (UAM-I). 2702 records from (Appendix B) Abundance of benthic foraminifera in sediment cores GIK17964-3 and GIK17964-2. 53 records from Squid collection from 1995/96 V4 BROKE. 5 records from Nannofossil abundance of Hole 29-278A. 49 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2005-2006. Part 1. 124 records from (Appendix A1) Cenomanian benthic foraminifera of ODP Hole 207-1258A. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 50 records from Total foraminifera counts of multinet M21/5_MSN743. 7 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_230-9. 10 records from Phytoplankton abundance at station Sechin_2003-08-06_2, Casma, Peru. 125 records from (Table 2) Absolute abundance of Contusotruncana contusa in DSDP Hole 74-525A. 51 records from Coccolith counts of multinet M32/5_MSN971. 4 records from Nannofossil abundance of Hole 10-89. 15 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-2. 81 records from Crustacea in surface sediments off Sylt collected during Heincke cruise HE272. 6050 records from CUBA: Herbario de la Academia de Ciencias, La Habana, Cuba: HAC-Pteridophyta. 742 records from (Appendix A) Relative abundances of smaller size planktonic foraminifera in latest Maastrichtian sediments of DSDP Hole 74-525A from Walvis Ridge, South Atlantic. 58 records from Occurrence of mammalia relicts at site Sandalja II. 17400 records from Sam Mitchel Herbarium of Fungi (Denver Botanic Gardens). 206 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 14 records from (Tab. 7) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 43-384, J-Anomaly Ridge, Grand Banks off Nefoundland. 1 records from Abundance of benthos infauna at station GIK23038-1. 65 records from Leben in und an der Ruwer sowie ihren Nebenbächen. 93 records from (Table 7) Relative abundance of benthic foraminifera in ODP Hole 112-683B. 1040 records from Foraminifera and ostracods profile from sediment core AV14_K2-3. 539 records from Bay of Puck dataset (EurOBIS). 495 records from Life Science National Tsing Hua University. 5 records from Trap data GBZ4, 696 m. 6 records from Microzooplankton abundance and biomass at station NBP97-08-33-5. 2224 records from Cambridgeshire & Peterborough Biological Records Centre - Cambridge Lichen group data held by CPBRC.. 308 records from Phytoplankton abundance during G. M. Dannevig cruise GMD91/10. 864 records from Lower Albian LArboudeysse (Niveau Paquier) range chart in percentages of nannofossils, in SE France. 3 records from Re-description of Cultroribula berolina Weigmann, 2006 (Acari, Oribatida, Astegistidae) from Germany with a key for the European species. 4 records from Ostracoda abundance of Hole 32-305. 458 records from PeECE I - Pelagic Ecosystem CO2 Enrichment Study, Raunefjord, Bergen, Norway, 2001. 1157 records from ISU Mammals. 1384 records from Bridel Herbar. 427 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Juergen Homeier. 679 records from Inventaire National du Patrimoine Naturel : Programme national espèces végétales de la Directive Habitat. 207 records from (Table 1) Stable isotope ratios of foraminifera in sediment core CH82-20. 2911 records from Distribution of foraminifera of sediment core GeoB1112-4. 10591 records from Planktic foraminifera (%) of sediment core MD97-2151. 1150 records from Macrozooplankton concentrations estimated from MOCNESS tow samples, Continental Margin Western Antarctic Peninsula, GLOBEC. 98 records from Distribution of planktonic foraminifera in DSDP Hole 90-594 east of New Zealand. 6 records from Occurrence of mammalia relicts at site Barova Cave. 228 records from Occurrence of mammalia relicts at site Grotte Scladina. 105 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 6414 records from Colección de referencia de vectores de Leishmania spp (causante de Leshmaniasis cutánea localizada) de la Península de Yucatán y un estudio preliminar en un área endémica de Quintana Roo. ECOSUR_SNIB. 761 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Walther Herwig cruise WH220. 170 records from (Fig. 3) Relative abundance of Emiliania huxleyi in sediment core MD99-2343. 1513 records from M. Gollop Collection. 40472 records from MEXU/Colección de Briofitas. 213 records from 4. Tag der Artenvielfalt, Naturschutzgebiet Hockenheimer Rheinbogen. 146 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 168 records from Occurrence of mammalia relicts at site Geißenklösterle. 12 records from Occurrence of mammalia relicts at site Dolni Vestonice. 201 records from Planktic foraminifera abundance of Hole 4-31. 1047 records from Planktic foraminifera abundance of Hole 21-206. 196 records from Foraminifera abundance of Hole 33-317A. 61 records from Range table from benthic foraminifers in ODP Hole 139-857B. 102 records from Range table from benthic foraminifers in ODP Hole 139-858A. 1 records from Dinoflagellate abundance of Hole 38-343. 805 records from Relativ abundances of live fauna of benthic foraminifera in surface sediments (Table C2.1). 33 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Stylops (BNHS) â 1930-1971. 859 records from Royal Horticultural Society - RHS berberis sawfly (Arge berberidis) monitoring. 150 records from Isotope age and relative abundance of planktonic foraminifera in Core Vulk-34-90, Sea of Okhotsk. 72704 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 373 records from Otter survey of Ireland 2004 & 2005. 53 records from Plasm bearing foraminifera counts from M35/1_MSN1058. 25 records from Phytoplankton abundance at station Sechin_2003-12-28_2, Casma, Peru. 1036 records from Benthic foraminifera distribution of sediment core ASV1200. 235 records from Klutensee. 4 records from Description of a new species of Labeo (Teleostei: Cyprinidae) from the lower Congo River.. 102 records from Planktic foraminifera abundance of Hole 67-498A. 2197 records from Benthic foraminifers of sediment core Svanic90_9004. 7920 records from Sinfonevada: Dataset of Floristic diversity in Sierra Nevada forest (SE Spain). 5164 records from Inventaire National du Patrimoine Naturel : Programme CARTHAM: Inventaire biologique dans le cadre de Natura 2000 en Mer. 152 records from Nematode abundances in sediments from the Nyegga pockmark area (Norwegian Sea) obtained during the VICKING expedition in 2006. 1300 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del río Cajambre (Guandal), municipio de Buenaventura, Valle del Cauca. 116 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Troglodytidae. 44 records from Solanum_baretiae. 1 records from A new Camponotus from Madagascar and a small collection of ants from Mauritius.. 233 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 37014 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Reptiles. 169 records from Planktic foraminifera counts at CTD station PS55/051. 26 records from Calcareous dinocysts in ODP Hole 80-550B, part 1. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_2-CTD1. 18 records from Phytoplankton abundance at station Rigel_6_2005-04 in April 2005, Chipana, Chile. 319 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the LÃ¬ and Coire Dhorrcail Estate during June 2001.. 164 records from Terrestrial molluscs at the Natural Park of the Serralada Litoral (Barcelona, Spain). 25592 records from Herbarium Amazonense. 1 records from A record of Anzygina billi Fletcher & Larivière, 2009 (Hemiptera: Cicadellidae) from New Zealand. 2000 records from Colección Científica de Referencia Zoológica del Chocó- Herpetología. 1 records from On centipedes (Chilopoda) of Albania, 2. 2 records from Parioglossus galzini, a new species of ptereleotrid dartfish from Rapa Island (Teleostei: Gobioidei: Ptereleotridae).. 22 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5116-2. 694 records from Gastropoda, scaphopoda and amphineura abundance of surface sediments of the Atlantic continental shelf off Southern Spanish Sahara, West Africa (Table 2). 55 records from "Schule am Inselsee" Güstrow. 48 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE218. 87 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2008. 850 records from Riqueza específica y biogeografía de los corales hermatípicos de la sección sur del Golfo de California y las Islas Revillagigedo. 65364 records from Mammals Specimens. 38 records from Microfossil abundance of Hole 21-206C. 1050 records from Relativ abundances of total live fauna of benthic foraminifera in surface sediments (Table C1.1). 11729 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Hymenoptera_Bombidae_Types. 915 records from Colección de Coleoptera (Tenebrionidae) del sureste de la Península Ibérica de la Universidad de Granada. 101 records from Naturgrundstück (Eutin). 40 records from Streuobstwiesengelände St.Meinrad Gymnasium. 141 records from Plasm bearing foraminifera counts from multinet SO119_MSN1282. 656 records from ZFMK Sound Archive. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/424-3. 356 records from MGC Herbarium of University of Malaga (Spain): MGC-Lichen dataset. 476 records from Caracterización Aves IAI-GAICA: Proyecto Cambio Climático. 254 records from BIRDRACE Thüringer Becken-Birders. 2196 records from Total fauna of benthic foraminifera of Hole 44-390A, Blake Nose Plateau, North Atlantic. 220 records from Total foraminifera counts of multinet SO118_MSN1253. 148 records from Total foraminifera counts from multinet SO119_MSN1278. 147 records from Plasm bearing foraminifera counts of multinet M21/2_MSN656. 137 records from Planktic foraminifera counts at CTD station PS55/030. 44 records from (Table IIIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean. 9 records from Microzooplankton abundance and biomass at station TT043_11-1. 470 records from Phytoplankton abundance during Lev Titov cruise LT90/5. 9 records from Nannofossil abundance of Hole 11-99A. 63 records from Planktic foraminifera counts of sediment core RC13-154. 240 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part I. 272 records from Dinoflagellate abundance of Hole 81-555. 2500 records from Zooplankton (NSMK-ZP). 100193 records from Mammalogy Collection - Royal Ontario Museum. 27 records from A new species of the gobiid fish Trimma from the Western Pacific and Northern Indian Ocean coral reefs, with a description of its osteology.. 42 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Passeridae. 111 records from Microplankton abundance measured on water bottle samples during AEGAEO cruise LIA-8. 73 records from Nannofossil abundance of Hole 73-520. 9 records from Numbers and dry weight of main macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 3). 6 records from Two new dolichoderine ant genera from Madagascar: Aptinoma gen. n. and Ravavy gen. n. (Hymenoptera: Formicidae).. 11 records from Nannofossil abundance of Hole 22-218. 484 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 117-726A. 13 records from (Table 3) Distribution of some benthic foraminifera in ODP Hole 108-659A. 21 records from (Table 3) Paleotemperature estimates for ODP Hole 105-646B. 1700 records from Nuevos registros de esponjas del Pacífico mexicano, Mar de Cortés y Archipiélago Revillagigedo. 1237 records from Nematode abundance in sediments obtained during RRS Charles Darwin cruise CD179. 27 records from Range table from planktonic foraminifers in ODP Hole 169-1036B. 50 records from Abundance of birds on the channels of Lena Delta in the nesting period. 131 records from Siliceous microfossil occurrence, Site 177-1092. 22 records from Anostomoides passionis, a new fish species from rio Xingu, Brasil (Characiformes: Anostomidae).. 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 9879 records from Bibliographic records of Angola mammals. 148 records from Faunal assemblage of sediment core GS7603-11. 13 records from Distribution of meiobenthos in sediment core M19_238-2 of the northeastern Atlantic (Table 1). 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 6 records from Nannofossil abundance of Hole 10-91. 5 records from Nannofossil abundance of Hole 67-498A. 18 records from (Table 2) Average major-element composition of glass shards from Toba Tephra Beds in Sumatra, Malaysia, India, and the Indian Ocean. 18 records from Akita Prefectural Museum＋Cnidarians Specimens of Akita Prefectural Museum. 230 records from Pilularia Globulifera distribution map in Denmark. 420 records from Phytoplankton abundance in surface water in November 1997, Ilo, Peru. 132 records from tab 2. 661 records from Vom Gipfel ins Moor, Transekt im NSG Allgäuer Hochalpen. 1 records from Arthropoden aus südostalpinen Höhlen.. 24972 records from Colección de Herbario. 10592 records from Wikander. 18 records from RSPB - Black grouse lek survey in Lothian and Borders, 2008 (RSPB). 216 records from (Table 1) Distribution of foraminifera in the Miocene section of ODP Hole 133-815A. 54 records from Herbier de l'Ecole Normale de Bourges (BOUM). 66081 records from HUFU - Herbarium Uberlandense. 6 records from (Table 3) Middle Eocene silicoflagellates from DSDP Hole 95-613. 355 records from Culture Collection of Cryophilic Algae. 1 records from Oribates mollicomus. 112 records from CommunicA Koblenz - Wildkräuterexkursion - Rheinsteig Bornhofer Höhe. 58 records from Schulgelände Kranich-Gymnasium (Salzgitter). 21 records from Bach. 165 records from Total foraminifera counts from multinet M31/3_MSN898. 17 records from Dinoflagellate cysts of sediment core IOW211630-9. 11 records from Nannofossil abundance of Hole 11-101. 7 records from Diatom abundance measured on water bottle samples at station PS58/107-5. 128 records from Coccoliths in sediment core PS1535-8. 20672 records from MSB Parasite Collection (Arctos). 741 records from Biogeographic distribution of Antarctic and sub-Antarctic Mysida. 15 records from Planktic foraminifera abundance of Hole 17-165. 111 records from Planktic foraminifera abundance of Hole 9-79A. 1 records from Planktic foraminifera abundance of Hole 54-424A. 1 records from Celaeno rhodomela. 371 records from Planktic foraminifera abundance of Hole 63-470. 1 records from Hypochthonius pallidulus. 5860 records from Loopkevers Grensmaas - Carabid beetles near the river Meuse in Flanders, Belgium. 304 records from John Muir Trust - Bryophytes of Glen Nevis Woods 1987-1988. 589 records from (Appendix B) Benthic foraminifera extinction group polpulation of ODP Hole 184-1146A. 57 records from Heidesee / Halle. 176 records from Total foraminifera counts of multinet M21/2_MSN656. 71 records from Microzooplankton abundance measured on water bottle samples at station PS58/107-5. 134 records from Coleoptera identified from the Bellot Street site, Greenwich, London. 142 records from MfN - Fossil vertebrates I. 2 records from Nannofossil abundance of Hole 1-4. 39835 records from Lichen herbarium, Trondheim (TRH). 365 records from Greater Manchester Ecology Unit - Distribution of Bats in Greater Manchester. 2091 records from Estudio florístico de las gramíneas de Zacatecas. 21680 records from Osaka Prefectural Minoh Park Insects Museum. 8684 records from Individual Sightings. 139 records from Planktic foraminifera assemblage in sediment core GIK23071-3. 808 records from (Table 2) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 113-690C on Maud Rise, Weddell Sea. 105 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB06 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 14 records from Occurrence of mammalia relicts at site Joint Mitnor Cave. 22 records from Planktic foraminifera abundance of Hole 6-48B. 3688 records from Clare Biological Records Centre dataset. 96 records from (Table 2) Neogene benthic foraminiferal community at DSDP Hole 95-613. 36 records from Ruhrwiesen Arnsberg, Klasse 9 und 10, Fachbereich Biologie. 19 records from Distribution of planktic foraminifera of sediment core GIK23059-3 at stadium 5.5. 31 records from Biological data measured on water bottle sampels at station AT_II-119/5_31-7. 1 records from Microzooplankton abundance and biomass at station TT050_4-7. 25 records from Ostracoda abundance of Hole 48-404. 1250 records from Colección de Crustáceos Macrobénticos del Golfo de México (ICMyL-DF, UNAM). 196 records from (Table 2) Distribution of planktonic foraminifera shells of different species in deposits from DSDP Hole 30-289. 66 records from Visual Plants (144.41.33.158) - Private collection of Thorsten Kroemer. 870 records from Percentages of planktonic foraminifera species in sediment core V22-38. 494 records from Biologische Station im Kreis Wesel. 258 records from Planktic foraminifera abundance of Hole 40-364. 84 records from Range table from planktonic foraminifers in ODP Hole 141-859B. 110 records from Range table from planktonic foraminifers in ODP Hole 144-875C. 13 records from Range table from benthic foraminifers in ODP Hole 194-1192A. 14522 records from MVZ Egg and Nest Collection (Arctos). 60 records from crocodylus. 114 records from RSPB - Tree sparrow recovery project â summary data, North West England, 2004-2010 (RSPB, NE, Wirral Borough Council, Cumbria Biodiversity Partnership). 33 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 113 records from Studies on species of Holarctic Pardosa groups (Araneae, Lycosidae). VII. The Pardosa tesquorum group. 3087 records from Herpetile collection, Natural History Museum, University of Oslo. 493 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 3. 172 records from Total foraminifera counts of multinet PO247/2_MSN1371. 2014 records from (Table 10) Distribution of planktonic foraminifers in ODP Hole 112-688A. 256 records from (Table 4) Distribution of Cretaceous calcareous nannofossils in ODP Hole 114-700B. 5186 records from Distribución conocida y potencial de 48 especies de hongos silvestres comestibles en la región central del país. 17 records from (Table 2) Distribution of Manumiella seelandica in Maastrichtian sediments of the Bass River Section in the southern New Jersey. 16 records from Occurrence of mammalia relicts at site Buchenloch. 1 records from Range table from planktonic foraminifers in ODP Hole 139-858F. 565 records from Range table from planktonic foraminifers in ODP Hole 180-1118A. 17450 records from The Scottish Ornithologists' Club - Fife breeding bird tetrad atlas 1991-99. 250 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 3082 records from dec2011. 3359932 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 73 records from A new handfish, Brachionichthys australis sp. nov. (Lophiiformes: Brachionichthyidae), with a redescription of the critically endangered spotted handfish, B. hirsutus (Lacepede).. 109102 records from Recent Invertebrates Specimens. 9526 records from UK Cetacean Strandings Investigation Programme - Stranded cetacean data from Great Britain collected from 01/01/89 through to 31/03/10. 517 records from Schulzentrum "Parc Hosingen". 94 records from FFH-Gebiet Paartal. 58 records from Plasm bearing foraminifera counts of multinet M12/3_MSN560. 15 records from Plasm bearing foraminifera counts of multinet PO231/3_MSN1330. 7 records from Planktic foraminifera counts of multinet M21/5_MSN732. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_8-CTD102. 40 records from Macrofauna biomass in surface sediment sampled during cruise DI226. 3800 records from (Figure 7) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-630A. 218 records from Planktic foraminifera assemblage in sediment core GIK16396-1. 2628 records from GEO Hauptveranstaltung Tirol (Innsbruck). 8 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1994-D4. 20 records from Range table from planktonic foraminifers in ODP Hole 175-1078C. 69907 records from CU Invertebrate Paleontology. 76 records from (Table T2) Calcareous nannofossil stratigraphy of ODP Hole 198-1214A. 18 records from Rita macracanthus, a new riverine catfish (Teleostei: Bagridae) from South Asia.. 4286 records from Inventaire National du Patrimoine Naturel : Atlas de la flore de Lorraine. 2476 records from EcoRecord - Bug (Hemiptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 7 records from Cordylancistrus nephelion (Siluriformes, Loricariidae), a new and endangered species of suckermouth armored catfish from the Tuy River, north-central Venezuela.. 80 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1361. 4 records from Microzooplankton abundance and biomass at station TT054_7-18. 9 records from Microzooplankton abundance and biomass at station NBP97-03-05-6. 641 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Northwest African upwelling area. 3718 records from Benthos counted on dredged samples during Valdivia cruise VA53. 242 records from Schieferbrüche. 110 records from Artenvielfalt und Kulturlandschaft. 14 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/048-3. 1010 records from Distribución y algunos aspectos ecológicos de hongos hidnoides estipitados de México. 11 records from (Table 2) Population density and zoobenthos biomass in bottom communities of the Novosibirsk Polynya in September 2008. 138 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV4. 9031 records from AIMS - LTM Nearshore Corals (OBIS Australia). 72615 records from Marine and Coastal Management - Demersal Surveys (years 1991-1995) (AfrOBIS). 3420 records from Nova Scotia Museum of Natural History, Halifax, NS, Canada. 5815 records from Coleoptera of Białowieża Forest. 33 records from Occurrence of mammalia relicts at site Gamssulzenhöhle. 60 records from Range table from benthic foraminifers in ODP Hole 139-858C. 104 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Motacillidae. 9 records from Polyrhachis (Myrma) cyaniventris F. Smith, 1858 (Hymenoptera: Formicidae) and a related new ant species from the Philippines.. 5116 records from Caracterización de la avifauna de las cuencas de los Ríos Cañas (Dibulla–Guajira), Garupal (Valledupar–Cesar), Arroyo Grande (San Juan de Nepomuceno–Bolívar), Aipe (Huila), Yaví (Tolima), Dagua (Valle del Cauca) como insumo para la identificación de oportunidades de conservación y de recuperación de servicios ecosistémicos del bosque seco.. 38 records from Plasm bearing foraminifera counts of multinet M21/5_MSN742. 845 records from Planktic foraminiferal assemblages of the Paleocene-Eocene Thermal Maximum from ODP Hole 198-1209B, Shatsky Rise, Pacific Ocean. 11 records from Distribution of meiobenthos in sediment core M19_232-2 of the northeastern Atlantic (Table 1). 23048 records from Herpetology Collection. 19 records from Cottus kanawhae, a new cottid fish from the New River System of Virginia and West Virginia.. 174 records from Birds (NHCA-BI). 7971 records from Monitoring records of plant species in the Hakone region of Fuji-Hakone-Izu National Park, Japan, 2001-2010. 78 records from (Table 10) Coiling ratio of Neogloboquadrina pachyderma of ODP Holes 127-794A and 127-197B. 17170 records from Herbier Louis-Marie (QFA) - Collection de bryophytes. 1 records from Arthropoden aus südostalpinen Höhlen.. 976 records from (Table T2) Planktonic foraminifera abundance of ODP Site 170-1040 sediments. 779 records from Guadeloupe_Ananas. 46664 records from The Scottish Ornithologists' Club - Fife non-breeding bird 5km atlas 1991-99. 28385 records from Plan de vertebrados de la Patagonia. 6 records from Review of the genus Metopheltes Uchida, 1932 (Hymenoptera, Ichneumonidae) with description of a new species from Vietnam. 1447 records from Odonata of the Congo River 2010 expedition. 600 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Accipitridae. 761 records from Dorset Environmental Records Centre - Dorset Heath - NBN South West Pilot Project Case Studies. 66 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 5 records from Feuchtwiese. 140 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 836 records from (Figure 4) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-626D. 140 records from Distribution of late Turronian planktonic foraminifers in ODP Hole 114-700B. 127 records from (Appendix E) Stable carbon and oxygen isotope composition of Globigerinoides sacculifera of ODP Hole 121-758B. 1534 records from PonTaurus collection. 655171 records from Bugbase, Lepidopterological Society. 10 records from Oberservation of birds at station PS14/149 along 49° West. 81 records from Revision of the snailfish genus Allocareproctus Pitruk & Fedorov (Teleostei: Liparidae), with descriptions of four new species from the Aleutian Islands.. 6 records from MfN - Micropaleontology. 30 records from Nannofossil abundance of Hole 94-608. 103 records from (Table 6b) Calcareous nannofossil distribution on ODP Hole 117-731C. 436 records from Larval fish at Helgoland Roads in 2005. 1272 records from (Table 2) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-706A. 5918 records from Catálogo y recopilación de datos científicos de los lepidópteros nocturnos de México, pertenecientes a cinco familias. 181 records from Marine Biological Association - RISC and ALERT Marine Non-Native Species (Chinese Mitten Crab, Wakame and Carpet Sea Squirt) Records. 58614 records from Marine and Coastal Management - Demersal Surveys (years 1986-1990) (AfrOBIS). 5 records from Range table from planktonic foraminifers in ODP Hole 171-1049C. 389 records from Inventaire National du Patrimoine Naturel : CBN Bailleul. 31 records from (Table 4) Abundance of under-ice amphipods on flat ice and ice ridges sampled during the 2005 Hidden Ocean expedition. 680 records from (Table 1) Distribution of larger benthic and planktonic foraminifers in ODP Hole 135-841B. 1030627 records from Phanerogamic Botanical Collections (S). 1284 records from Collection of Heteroptera. 16 records from (Table V) Distribution of diatoms in samples from Heidemann Valley trench, Antarctica. 3 records from Sarcodine counts and carbon biomass at station TT011_5-CTD64. 1151 records from Coccolithophores in surface sediments of the Arabian Sea (TAble 1). 29 records from Range table from ostracoda in ODP Hole 151-911A. 73 records from Planktic foraminifera counts of sediment core V24-28. 54 records from Species occurring in the mytilid and alvinellid communities within the 9°N hydrothermal field at the East Pacific Rise. 753 records from Estación Experimental de Zonas Áridas (CSIC) EEZA-Mamif. 140 records from Occurrence of mammalia relicts at site Jägerhaus-Höhle. 1017 records from Broadland Environmental Services Limited - Water vole distribution within Broadland (2003-2006): based upon field signs, sightings and trapping data.. 140 records from Plant Living in Water (KIDR-PL). 2 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 5 records from (Table T5) Calcareous nannofossil stratigraphy of ODP Hole 198-1212B. 1 records from Oribates fusifer. 1496 records from Countryside Council for Wales - Stoneworts in Wales. 6060 records from Free-living Nematodes from Patagonia coastal lagoons (Chubut, Santa Cruz, Argentina).. 1 records from A new myrmicine ant genus from Malaysia with uncertain affinities (Hymenoptera: Formicidae).. 217 records from Birdrace-Ornis_im_Einsatz-Lahn-Dill-Kreis. 857 records from Artenvielfalt am Eich-Gimbsheimer Altrhein. 17 records from (Table 3) Nannofossil occurrence in the Albian of ODP Hole 101-635B. 1 records from Mesozoa - SMF. 1360 records from Contribución a la riqueza ictiofaunística de la Reserva de Ría Lagartos, Yucatán. 9 records from Foraminifera abundance of Hole 64-477A. 569 records from Benthic foraminifera abundance of Hole 84-567A, Part 2. 128 records from (Table 2) Distribution of ebridians and actiniscidians in selected samples from DSDP Hole 90-591. 33 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 174-1071F. 420 records from Phytoplankton abundance in surface water in January 1996, Ilo, Peru. 18959 records from Herbarium Specimens of Bonin and Ryukyu Islands. 10 records from Succession of benthic hard-bottom communities abundance at Liliguapi in 2010. 106 records from Rare vascular plant species in North-West of Kostroma region, Russia. 4076 records from HUCO - Herbário da Universidade Estadual do Centro-Oeste. 51 records from (Table 1) Total cyst counts and concentrations of dinocysts and pollen together with environmental parameters. 384824 records from Herbarium, Botanical Museum, University of Oulu, Finland (OULU). 559 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Meiofauna. 37986 records from rmca-albertine-rift-cichlids. 10 records from Occurrence of mammalia relicts at site Adler Cave xx. 44 records from Planktic foraminifera abundance of Hole 19-188. 244 records from Range table from benthic foraminifers in ODP Hole 145-887C. 1 records from Microfossil abundance of Hole 42-378. 13 records from Environment Agency - Environment Agency white-clawed crayfish Survey of the River Lune Catchment 2004. 1353 records from Colección de Entomología - Diptera - Ceratopogonidae. 13583 records from Highland Biological Recording Group - HBRG Fungus, Lichen and Lower Plants Dataset. 2 records from Hornmilben (Oribatida) [pages 323 to 417]. 40 records from Flächennaturdenkmal Grubditz. 172 records from Leben im Finkensteiner Moor. 10 records from Ökowerk Emden. 174 records from BIRDRACE Bon(n)apartemöwen. 442 records from Distribution of planktic foraminifera of sediment trap NB7. 89 records from Total foraminifera counts from multinet SO119_MSN1303. 48 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 8 records from Abundance of radiolaria at station LV28-29-1. 601 records from LBV 100 - Artenvielfalt am Rothsee. 2 records from Nannofossil abundance of Hole 9-82. 21 records from Meiofauna abundance in sediment core 12930-018. 32 records from Grundschüler erkunden Schulumgebung. 7926 records from NBM birds. 64240 records from The Scottish Ornithologists' Club - South East Scotland Tetrad Atlas 1988 - 1994 - non-sensitive breeding species. 12 records from Phytoplankton abundance in surface water in October 1995, Ilo, Peru. 1 records from Abundance of benthos infauna at station GIK23062-2. 510 records from (Table S2) Relative abundance of coccolithophora in sapropel S1 of ODP Hole 160-964B, filtering preparation. 10633 records from Biological Records Centre - Collembola Recording Scheme. 8 records from Microzooplankton abundance and biomass at station TT045_29-1. 21 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD56. 138 records from Phytoplankton abundance at station DI182_11863#1. 9 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/043-2. 14278 records from (Table 4) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-700B. 96 records from (Table 1) Distribution of calcareous nannofossils in ODP Hole 113-689B. 1359 records from GEO Biodiversity Day. 3015 records from Bird specimens in Gifu Prefectural Museum. 155 records from Bergbaufolgelandschaft am Muldestausee. 237 records from Planktic foraminifera abundance of Hole 21-207. 1756 records from Relative abundances of middle Pleistocene benthic foraminifera in DSDP Site Site 90-594. 19 records from (Table 6) Pleistocene nannofossil range chart for ODP Hole 134-830A. 31 records from Pastinachus solocirostris sp. nov., a new species of Stingray (Elasmobranchii: Myliobatiformes) from the Indo-Malay Archipelago.. 1 records from Nothrus canaliculatus. 1429 records from Morano and Cardoso: AraIb. 10 records from Description of the females of Anapis castilla and Anapisona bordeaux (Araneae, Anapidae).. 83 records from Spechtwald. 26417 records from Diveboard - Scuba diving citizen science observations. 43 records from Plasm bearing foraminifera counts of multinet M21/5_MSN734. 160 records from Total foraminifera counts of multinet M21/2_MSN658. 32 records from Biological data measured on water bottle sampels at station AT_II-119/5_35-4. 5 records from Microzooplankton abundance and biomass at station TT050_7-9. 12 records from Phytoplankton abundance at station Casma_2003-04-14_1, Casma, Peru. 234 records from Baggerseen bei Krauchenwies. 1 records from Schneifelkinder erkunden südliche Blumenpracht. 2048 records from (Table 5) Distribution of planktonic foraminifers in ODP Hole 108-659A. 70 records from Korean Aquatic Vascular Plants. 9674 records from Mammal collection of National Museum of Nature and Science. 4550 records from University of Alberta Museums, Freshwater Invertebrate Collection. 366 records from Marine fauna survey of the Vestfold Hills and Rauer Island, 1981-82. 323 records from Foraminifera abundance of sediment core IN68-29. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station AUGUST-1994-D2. 80 records from Planktic foraminifera abundance of Hole 49-411A. 4 records from Range table from planktonic foraminifers in ODP Hole 171-1049A. 612 records from Range table from benthic foraminifers in ODP Hole 149-900A. 593 records from Mamíferos voladores laguna El Tinije. 356 records from Amphibia Collection of Museum and Institute of Zoology PAS. 448 records from Biodiverisity Group, Dept. of Environment, Food and Agriculture,Isle of Man Government - Japanese Knotweed Records in the Isle of Man 1991-2008. 164233 records from ORN. 9 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE233. 1577 records from (Table 2) Stratigraphic distribution of dinocyst taxa in ODP Hole 150-903A. 9271 records from APIS - Antarctic Pack Ice Seals 1994-1999, plus historical data from the 1980's. 33944 records from Aranzadi Zientzi Elkartea. 83 records from Visual Plants (144.41.33.158) - Private collection of Juergen Homeier. 617 records from (Table 5) Realtive abundance of planktonic foraminifera in sediment core AHF-11343. 142 records from Birdrace-Alte_Socken-Cuxhaven. 147 records from Planktic foraminifera abundance of Hole 22-217. 88 records from Dinoflagellate abundance of Hole 28-274. 264 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 1031 records from (Table 4) Carbon flux, paleoproductivity, relative abundance of foraminifera on sediment core PS2837-5. 149 records from Naturnahes Tal in Siena. 1 records from Collection Mammalia fossil SMF. 29 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM7. 10 records from Devon Biodiversity Records Centre - Devon giant hogweed data 1997 to 2000. 271 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 71 records from Birdrace-do_elster_Dortmund. 9062 records from Northern Biodiversity Program Coleoptera (2010-2011). 18 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001I. 519292 records from Museum Victoria provider for OZCAM. 49 records from Total foraminifera counts of multinet M10/2_MSN238. 197 records from Total foraminifera counts of multinet M21/1_MSN608. 856 records from Planktic foraminifera counts of sediment core V27-178. 3253 records from ISU Birds. 1177 records from Phytoplankton abundance during Mikhail Lomonosov cruise ML47. 11 records from A new species of Probolomyrmex from Madagascar.. 63 records from (Fig. 9A) Compiled data of profile L´Arboudeysse, SE France. 1 records from Nouvelles fourmis de l'Imerina oriental (Moramanga etc.).. 221 records from (Table T2) Calcareous nannofossil abundance of ODP Hole 171B-1052A sediments. 104 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cathartidae. 336 records from Planktic foraminifera counts of sediment core V19-185. 380 records from Stable oxygen and carbon isotope ratios of Globigerinoides obliquus of quantitative range chart of the ostracodes in the Pliocene-Pleistocene interval of ODP Hole 107-654A. 387 records from Distribución espacio-temporal de las larvas de atunes en el Golfo de Tehuantepec, México. 127499 records from Southern Ocean Continuous Zooplankton Recorder (SO-CPR) Survey. 207 records from Geo-Tag der Artenvielfalt Süßen Hornwiesen-Grundschule. 685 records from Planktic foraminifera abundance of Hole 4-30. 260 records from Range table from planktonic foraminifers in ODP Hole 155-930D. 1088 records from Relativ abundances of total dead fauna of benthic foraminifera in surface sediments (Table C1.2). 59316 records from JPB - Herbário Lauro Pires Xavier. 49 records from A catalogue of the ants of Paraguay (Hymenoptera: Formicidae).. 232 records from (Table A1) Stratigraphic distribution of calcareous nannofossils of ODP Hole 198-1210A. 74 records from Schulwald Grundschule Brügge. 111 records from BIRDRACE Die Wendehälse. 40 records from Plasm bearing foraminifera counts from M35/1_MSN1057. 2 records from Nannofossil abundance of Hole 1-5A. 60000 records from Birds (NSMK-BI). 218 records from GTI MICROFUNGI OBSERVATION. 197 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: MAMMALIA_FZ. 332 records from Foraminifera distribution of sediment core SDSE192. 67371 records from Swedish Board of Fisheries (Fiskeriverket) - Swedish Electrofishing Registry. 63985 records from The First Atlas of Breeding Birds in Britain and Ireland: 1968-1972.. 415 records from Dinoflagellate cysts from the Upper Hauterivian (Cretaceous) of a claystone-marlstone succession in the clay-pit Frielingen. 1371 records from (Table T2) Abundance of dinoflagellates and other palynomorphs in Eocene-Oligocene sediments from ODP Hole 189-1172A. 30926 records from Annelida collection of National Museum of Nature and Science. 33 records from (Table 6) Distribution and abundance of calcareous-nannoplankton species in the Cretaceous sediments of DSDP Hole 62-466. 112 records from Abundance of dead benthic foraminifera in sediment core CD86_06_BC5. 1431 records from (Figure 6) Benthic foraminifera counts of sediment core MD01-2378. 94 records from Total foraminifera counts from M35/1_MSN1074. 17 records from Dinoflagellate cysts of sediment core IOW211630-9. 1 records from Zetes dorsatus. 39033 records from SBMNH Vertebrate Zoology. 14 records from Relative abundance of live benthic foraminifera of sediment core M5/2_91MC. 16632 records from BANDAPHO, BAse de DAtos sobre Aphodiidae. 75 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 798 records from Biological Records Centre - Irish Otter Dataset. 16 records from Mollusca Colelction of the Seto Marine Biological Laboratory, Kyoto University. 25128 records from rmca-albertine-rift-butterflies. 11 records from Nannofossil abundance of Hole 3-15. 2 records from Nannofossil abundance of Hole 3-18. 28 records from Apectodinium, age and percentage of endemic and bipolar dinoflagellate cysts of ODP Hole 189-1171D. 11981 records from SMNK Mantid Collection. 206 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto) Herpetofauna. 104 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto) Murcielagos. 44501 records from Canadian National Collection (CNC) of Insects, Arachnids and Nematodes. 34 records from Meiofauna abundances in sediments from the Nyegga pockmark area (Norwegian Sea) obtained during the VICKING expedition in 2006. 601 records from Distribution of planktic foraminifera (112-200 µm) of sediment core M8_057-2 (Table 5). 4 records from Pycnogonida collection of National Museum of Nature and Science. 2255 records from Plant Systematics Laboratory, Ajou University, Korea. 135 records from Birdrace_Dith_MarshSandpiper-Dithmarschen. 116 records from Occurrence of mammalia relicts at site l´Abri de la Ferrassie. 389 records from Planktic foraminifera abundance of Hole 23-228. 496 records from Range table from benthic foraminifers in ODP Hole 145-887A. 36 records from Range table from benthic foraminifers in ODP Hole 160-967E. 281 records from (Table 1) Ostracoda community from DSDP Hole 95-612. 1735 records from Naturalis National Natural History Museum (NL) – Acari_Types. 396314 records from British Lichen Society - BLS Lichen Database: English churchyards. 9 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_209-1. 11 records from Microzooplankton abundance and biomass at station TT045_15-2. 1 records from Microzooplankton abundance and biomass at station TT050_24-13. 12 records from Phytoplankton abundance in surface water in 2004, Ancon, Peru. 5 records from Distribution of meiobenthos in sediment core M19_216-2 (2) of the northeastern Atlantic (Table 1). 491 records from Naturschutzgebiet Lüneburger Heide. 100125 records from Ohio State University Fish Division (OSUM). 56051 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 91 records from CNIN/Tipos Homoptera. 149 records from Biotop Binsenwiesen (Wehrheim/Taunus). 11 records from Occurrence of mammalia relicts at site Nörre-Lyngby. 2467 records from Coleccion Herpetologica Reptiles LJAMM-CNP. 850 records from (Table 3) Distribution of benthic foraminifers from ODP Hole 134-828A. 7403 records from Freshwater fishes of Hidalgo state (Mexico) in the MZNA fish collection of the University of Navarra (Spain). 632 records from MVZ Hildebrand Collection (Arctos). 6 records from Der Wiesenpark in Oschersleben - ein Arboretum mit eigener Ästhetik. 48 records from Heider Bergsee (Brühl). 26559 records from Taiwan Forestry Research Institute. 25830 records from Colección de Diatomeas del Sur del Golfo de México (ICMyL-DF, UNAM). 8 records from Description of lithologic section units of IODP Hole 325-M0049B. 14219 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 4288 records from Universitat de Girona: HGI-Cormophyta. 13865 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF-Lich. 1664 records from Zooplankton of the Eastern South Pacific (OBIS South America, SOUTH PACIFIC NODE). 87075 records from Banc de dades de biodiversitat de Catalunya-ArtroCat. 534 records from (Appendix B) Total cyst counts, and abundances of Selenopemphix undulata sp. nov. in Pacific Ocean surface samples. 2782 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Taminango, Nariño. 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 46 records from 8c. 133 records from Total foraminifera counts of multinet PO231/3_MSN1334. 61 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/546-19. 137 records from Abundance of planktic foraminifera at CTD station PS55/077-1. 340 records from Phytoplankton abundance and species composition in the Gulf of Naples from February to December 1987. 219 records from INERA-Luki reservation herbarium (CABIN project). 1001 records from Naturhistorisches Museum Mainz, Botanical Collection. 4000 records from Fungal Collection of Natural History Museum and Institute, Chiba. 7 records from Analyses of the recent components of sediment core PS1220-3. 759 records from Planktic foraminifera abundance of Hole 47-398D. 139 records from Range table from planktonic foraminifers in ODP Hole 139-855A. 73 records from Benthic foraminifera abundance of Hole 80-550. 162 records from (Fig. 2) Abundance of Uvigerina pygmaea in sediment core MD95-2039. 89 records from Dixidae (Diptera) of Ireland. 8527 records from HSU Wildlife Birds. 3946 records from EcoRecord - Amphibian records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 150417 records from Natural History Museum, Vienna - Herbarium W. 192 records from (Table 2) Relative abundance of selceted benthic foraminifera taxa of DSDP Hole 93-605. 97 records from (Table 1) Distribution of calcareous nannofossils in ODP Hole 167-1017E sediments. 1 records from Oribates gilvipes. 477 records from (Table 2) Distribution of foraminifera in the Miocene section of ODP Hole 133-816A. 12 records from Schulgelände Erich-Kästner-Schule. 14 records from Assemblage of living benthic foraminifera in sediment core CD146_55916#1, >150 µm. 141 records from Phytoplankton abundance at station CD47_3105C#4. 11 records from Phytoplankton abundance at station Sechin_2003-08-06_1, Casma, Peru. 130 records from Abundances of dinoflagellate cysts in sediment trap MST-9 (Appendix 1). 256 records from Planktic foraminifera counts of sediment core V16-20. 2077 records from Vascular plant specimens of Iida City Museum. 224 records from Bizzenbach-Aue im Bizzenbachtal (Wehrheim/Taunus). 78 records from Occurrence of mammalia relicts at site Einhornhöhle. 165 records from Foraminifera abundance of Hole 48-406. 298 records from Results of palynological analysis of Hole 302-M0002A. 32 records from A review of the subfamily Acaenitinae Förster, 1869 (Hymenoptera, Ichneumonidae) from Ukrainian Carpathians. 45 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 202 records from Inventario de Aves Buenos Aires, Tauramena, Casanare. 8 records from Krittenhorster Wald (Ostkilver). 157 records from Total foraminifera counts of multinet M21/6_MSN787. 11 records from Nannofossil abundance of Hole 55-431A. 142 records from Total foraminifera counts of multinet M21/2_MSN649. 43 records from Nannofossil abundance of Hole 11-102. 27 records from (Table 12) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-688A. 72 records from (Table 1) Distribution of silicoflagellates, actiniscidians, and ebridians in selected samples from ODP Hole 112-682A. 38 records from (Table 19) Nannoplankton distribution in sediment core ANS3-T9. 5 records from Analyses of the recent components in the sand fraction of sediment core PS1422-1. 298 records from Stausee (Oberdigisheim/Meßstetten). 24 records from Occurrence of mammalia relicts at site Fuchsloch im Krockstein. 28 records from Planktic foraminifera abundance of Hole 31-301. 54 records from Range table from planktonic foraminifers in ODP Hole 141-862A. 3525 records from Countryside Council for Wales - Important Welsh Bat Roosts Database (BATSITES-WALES). 198044 records from Naturalis Biodiversity Center (NL) - Botany Utrecht. 57218 records from National Biodiversity Data Bank. Observation records, 1900-2014. 13086 records from Collection of Coleoptera. 365 records from Colección Herpetológica de la Patagonia. 125572 records from NINA insect database. 1077 records from BioGIS - Fish - HUJ collections. 141 records from Plasm bearing foraminifera counts of multinet M21/1_MSN604. 27 records from Naturgarten Vielfalt - Naturlehrgarten Fa. Dehner. 208 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 265 records from Geometry of coccolith Gephyrocapsa in sediment core K708-007. 2 records from Nannofossil abundance of Hole 20-199. 574077 records from LACM Vertebrate Collection. 16 records from Phytoplankton abundance during Professor Siedlecki cruise PSied90/1. 111991 records from Monitoring data from the federal state North Rhine-Westphalia (Germany). 177239 records from Inventaire National du Patrimoine Naturel : Données ONEMA sur les poissons et écrevisses d'eau douce.. 21 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rynchopidae. 11371 records from Herbario Museo de La Salle Bogotá (MLS). 8 records from Kleiner Ziergarten Winzingen (Neustadt). 44 records from NW-Innenhof Gesamtschule Herten 7.6.2001. 164 records from Abundance of planktic foraminifera at CTD station PS55/066. 9 records from Distribution of hydropolyp species on coral reefs of the Red Sea (Table 5). 74 records from Description of a new Batrochoglanis species (Siluriformes, Pseudopimelodidae) from the rio Paraguai basin, State of Mato Grosso, Brazil.. 165 records from (Table 1) Palynomorph concentrations in ODP Hole 105-646B samples. 22 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB03 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 177 records from (Table 11) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-589. 220 records from Foraminifera abundance of Hole 57-440. 4196 records from Planktic foraminifera abundance of Hole 37-334. 35 records from Planktic foraminifera abundance of Hole 67-499A. 14 records from Benthic foraminifera abundance of Hole 96-620. 182 records from Relative abundance of live benthic foraminifera of sediment core M5/2_88MC. 107 records from (Figure 8) Distribution and character of selected biogenic and lithologic components at DSDP Hole 79-547A. 101662 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 122 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Site 198-1213. 50834 records from Institute of Dendrology PAS, Flora of Sudety Mountains. 19 records from Inventario de Aves Pauto J, Yopal, Casanare. 36432 records from RSPB - Corncrake national surveys - raw data (SCARABBS). 179 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cuculidae. 1100 records from (Table AT3) Planktonic foraminiferal stratigraphy of ODP Hole 182-1128B. 1998 records from Institut Botanic de Barcelona, BC-Lichenotheca. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD10. 7 records from Phytoplankton abundance at station Casma_2003-02-27_2, Casma, Peru. 265 records from Luderbusch. 47 records from Nannofossil abundance of Hole 64-479. 5 records from Nannofossil abundance of Hole 34-320A. 12 records from Diatom abundance measured on water bottle samples at station PS58/012-5. 5 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB06 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 7 records from A revision of the Aphaenogaster phalangium complex (Hymenoptera: Formicidae: Myrmicinae).. 7 records from Grundschule Sandheide. 76 records from Fish (MNHM-PI). 265 records from AIS Wildtype Populations of Arabidopsis. 1868 records from Inventario florístico de la Sierra de San Carlos, Tamps. 103 records from Invertebrate collections. 2 records from Nannofossil abundance of Hole 16-157A. 10030 records from Free-living marine Nematodes from San Julián bay (Santa Cruz, Argentine), 2009.. 39 records from Südpark (Bochum-Wattenscheid). 117 records from Plasm bearing foraminifera counts of multinet M21/1_MSN619. 9 records from Microzooplankton abundance and biomass at station TT043_2-1. 14 records from Phytoplankton abundance during Arne Tiselius cruise AT90/1. 310 records from Planktic foraminifera counts of sediment core V18-191. 247 records from Planktic foraminifera abundance of Hole 63-471. 121 records from Range table from planktonic foraminifers in ODP Hole 167-1011B. 145171 records from DUKE Bryophyte Collection. 908 records from (Appendix A1) Planktonic foraminifera of ODP Hole 157-951A. 970 records from BoBO - Botanic Garden and Botanical Museum Berlin-Dahlem Observations. 23227 records from Mollusk data of Molltax, Norway. 1 records from Review of the ant genus Nesomyrmex (Hymenoptera: Formicidae: Myrmicinae) in southern Africa.. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_10-CTD124. 6 records from Bayerische Donau - Metten. 126 records from (Table 2) Calcareous nannofossil distribution and relative abundance in ODP Hole 114-703A. 6912 records from Bryophyte Collection of Natural History Museum and Institute, Chiba. 47 records from Distribution of calcareous nannofossils in the lower sequence of the CIROS-1 sediment core (Table 2). 2731 records from (Appendix B) Percentages, total flux and fragmentation index of planktic foraminifera for core T89-40, Walvis Ridge (SE Atlantic). 1 records from On the Chilopoda from Turkey. 4 records from Nannofossil abundance of Hole 74-526B. 232 records from Polychaetes in surface sediments off Sylt collected during Heincke cruise HE278. 18894 records from (Table 5) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Site 114-702. 5 records from Loricifera - SMF. 86 records from Pollen analysis of sediment core GIK16856-2. 5323 records from Anfibios y reptiles del estado de Nuevo León. 6 records from Description of lithologic section units of IODP Hole 325-M0054B. 72316 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1993) (AfrOBIS). 333 records from Langes Tannen (Uetersen). 114 records from Range table from planktonic foraminifers in ODP Hole 171-1052F. 492 records from Phytoplankton abundance in surface water in October 1997, Chimbote, Peru. 82 records from Countryside Council for Wales - Non-native species records from Countryside Council for Wales (CCW) non-native monitoring research and ad-hoc sightings. 637 records from Countryside Council for Wales - Lamprey Survey Data. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 177494 records from Segundo censo de plantas leñosas de una Parcela Permanente de 25 hectáreas, ubicada en la Reserva Natural La Planada (Nariño, Colombia). 10 records from Two new species of eelpouts (Teleostei, Zoarcidae) of the genus Seleniolycus from the Ross Dependency, Antarctica.. 43 records from Relative abundance of planktic foraminifer Globigerinita uvula in core PS1243. 1 records from Nothrus biurus. 14212 records from MOSS - Herbário Dárdano de Andrade Lima. 66 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Aramidae. 105 records from People's Trust for Endangered Species - Noble Chafer: Pre-BAP records prior to 1998. 197 records from Inventaire National du Patrimoine Naturel : CBN Aquitaine-Poitou-Charentes. 2814 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 366 records from Weinberg Reichersdorf. 43 records from Schulgelände Thurmair-Gymnasium. 17 records from (Table 3) Stratigraphic distribution of silicoflaggelates, ebridians and actiniscidians in upper Pliocene to Pleistocene sediments of ODP Hole 104-644A. 606 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. Plantas. 43905 records from Herbarium of Jyväskylä University Museum. 12 records from Abundance of microplankton from bottle APRIL-2000-K1. 198 records from Microplankton abundance in the euphotic zone of the Aegean Sea in September 1994. 2346 records from (Fig. 8) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 44-391C in the North Atlantic. 12321617 records from Norwegian Species Observation Service. 41 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto129-136. 23593 records from New Zealand Biodiversity Recording Network. 968 records from TTRS Mammals. 1326 records from (Table T9) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones P5-P7. 262155 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 2 records from Note tassonomiche e faunistiche su Chilopodi della Grecia (Chilopoda). 2 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2010. 270 records from Meiofaunal abundance in sediments obtained during RRS Charles Darwin cruise CD179. 5 records from Schulinnenhöfe (Gelsenkirchen). 82 records from Plasm bearing foraminifera counts of multinet M27/2_MSN883. 88 records from P. W. Lund collection in the National History Museum of Denmark, Copenhagen. 63504 records from UNSM Vertebrate Specimens. 479 records from CBS Bacteria Database. 17 records from Nannofossil abundance of Hole 85-572D. 641 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during LITTORINA cruise LI1986/1. 168582 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Lepidoptera Observation Records. Pre-2010 for Cumbria. 17413 records from Herbarium BSG Vascular Plants. 12963 records from Composition of planktonic foraminifera species from 310 sediments samples during the last glacial maximum. 362 records from (Table A.05) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (100-150 µm). 8 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5. 3 records from Occurrence of mammalia relicts at site Igstadt I. 76 records from Occurrence of mammalia relicts at site Vindija. 46 records from Palynomorph data and remarks on dominant tree taxa from IODP Hole 313-M0028A. 62 records from Occurrence of mammalia relicts at site Pestera Livadita. 20 records from Review of the Camponotus aureopilus species-group (Hymenoptera, Formicidae), including a second Camponotus with a metapleural gland.. 2318 records from Fundación Miguel Lillo - Colección Ictiológica. 9216 records from Inventaire National du Patrimoine Naturel : Crustacés Décapodes de France. 36135 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 16 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 101 records from Assemblage of total living benthic foraminifera in sediment core SO119_MC501. 48 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1197. 14897 records from Rådgivende Biologer. 757 records from Sistemática y biogeografía del género Xenosaurus (Squamata: xenosauridae). 103178 records from MfN - Heteroptera Collection. 169278 records from herpetology. 1 records from Planktic foraminifera abundance of Hole 8-73. 94 records from Planktic foraminifera abundance of Hole 63-468A. 24 records from Range table from planktonic foraminifers in ODP Hole 146-889B. 2511 records from (Table T5) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1052E. 16 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rostratulidae. 10358 records from Census of the flora of Benin. 9173 records from Colección de líquenes del Herbario "Jaime Andrés Rodríguez". LEB-Lichen. 18 records from Landschaftsschutzgebiet Buchhorst2. 1297 records from Dinoflagellate assemblage in surface sediments of the South Atlantic. 1 records from Microplankton counts and carbon biomass at station TT007_8-CTD99. 92 records from Abundance of coccosphere-units of site GIK23259. 48114 records from MMNH Museum Bird Collection. 54 records from Occurrence of mammalia relicts at site Rusenschloß. 20 records from Foraminifera abundance of Hole 58-442B. 4 records from Dinoflagellates, pollen and spore abundance of Hole 29-282. 951 records from (Fig. 4) Downcore variations of selected planktonic and benthic foraminifera, calcareous nannofossils, and radiolaria in the Kirchrode I borehole. 64 records from (Table 3) Distribution of calcareous nannofossils in Cretaceous sediments recovered in ODP Site 129-801. 19 records from Assemblage of living benthic foraminifera in sediment core CD145_55803#5, >150 µm. 100 records from Foraminifera species abundances from tow TT011_12-MOC74. 337 records from Abundance of calcareous dinocyst along profile Calais-Escalles. 1 records from Microplankton counts and carbon biomass at station TT008_4-TM3. 10 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB6. 15 records from Die geheimnisvolle Welt der Spinnen. 53 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 63-125 µm. 94 records from Total foraminifera counts of multinet PO231/3_MSN1333. 13 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 16 records from Dinoflagellate cysts of sediments core IOW211660-6. 11 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_806-1. 3 records from Sarcodine counts and carbon biomass at station TT011_6-CTD71. 45 records from (Table S2) Age determination of ODP Sites 202-1234 and 202-1235. 753 records from Range table from ostracoda in ODP Hole 144-872C. 2392 records from (Table 3) Dinocyst ranges in ODP Hole 104-642D. 10 records from (Table 3) Minerals and components of sediments from DSDP Site 94-609_Site, North Atlantic. 11 records from Pollen profile Märchenwald C, Harz, Germany. 3 records from Akita Prefectural Museum＋Millipedes Specimens of Akita Prefectural Museum. 30246 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 763 records from Planktic foraminifera assemblage in sediment core GIK17050-1. 63 records from Planktic foraminifera assemblage in sediment core GIK23243-2. 414 records from Naturschutzstation Schmidsfelden. 10 records from Occurrence of mammalia relicts at site Aveley. 387 records from Planktic foraminifera abundance of Hole 63-467. 14411 records from Jardín Botánico Atlántico, Gijón: JBAG-Laínz. 3471 records from Collection Foraminifera SMF. 324 records from Tentaculata collection of National Museum of Nature and Science. 250 records from BATS & The Millennium Link - Bat records associated with the Union and Forth & Clyde canals (Period 2000 to 2005). 87 records from Artenvielfalt des "Grünen Klassenzimmers". 1 records from Range table from planktonic foraminifers in ODP Hole 174-1072A. 6686 records from Observaciones de Especies Silvestres (by Charif Tala). 179 records from (Table 4) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 129-801A. 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 26 records from Schulteich Heinrich-Mann-Schule. 256 records from BIRDRACE Upupa epöpse. 790 records
Keywords: GBIF; biodiversity; species occurrences